Engineering-practice-oriented digital twins for smart water management: Framework, enabling technologies, and future directions - Haozheng Wang; Jinkuo Li; Xuhui Dang; Baoyi Zhong; Rui Zhao; Xiaoxiang Wang; Chotiwat Jantarakasem; Guangtao Fu; Dragan Savic; Jun Ma; Yumeng Zhao (Water Research, 2027)

Enhancing Cr(VI) bioreduction via Na+-stimulated intracellular energy metabolism and electron transfer using methane as electron donor - Lianfu Liang; Xiaofeng Fu; Yuqing Ding; Keying Liu; Rui Lin; Zhaojin Chen (Bioresource Technology, 2027)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Biochar enhances anaerobic oxidation of methane coupled with Cr(VI) reduction: Pyrolysis temperature-dependent electron transfer pathways and regulatory mechanisms - Lianfu Liang; Yepu Li; Xiaofeng Fu; Rui Lin; Keying Liu; Zhiqiang Zhao (Bioresource Technology, 2026)

Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Dual-scale flower detection and homography-guided cluster matching for robotic pollination in trellised kiwifruit orchards - Leilei He; Bo Jia; Juncai Huang; Rui Li; Spyros Fountas; Longsheng Fu (Biosystems Engineering, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Hierarchical assembly of sub-1 nm nanowire for the construction of aerogels - Yuxiang Du; Xin Yang; Xiuqin Mei; Ran Du; Dan Liu; Changqing Miao; Rui Fu; Huazheng Sai (Chemical Engineering Journal, 2026)

Silica‑calcium composite amendments increase the erosion resistance of soda saline-alkali soils under consecutive extreme rainfall events - Zhuo Tian; Dongli She; Weidong Liang; Hongde Wang; Rui Fu; Shuo Wang; Yinhao Bai (CATENA, 2026)

Addressing the protein challenge in aquaculture: Nutritional attributes, application bottlenecks and refinement strategies for single-cell protein - Jiayv Zhang; Shanfei Fu; Rui Li; Mengxue Li; Zhenni Cheng; Xiaolei Fan; Rongbo Guo; Haiqing Wang (Animal Feed Science and Technology, 2026)

Seismic-induced bearing uplift in long-span deck-type arch bridges: Analysis and mitigation under near-fault ground motions - Maojun Yuan; Lueqin Xu; Da Fu; Rui Jiang; Longhua Zeng; Jianting Zhou (Soil Dynamics and Earthquake Engineering, 2026)

Molecular-level source contribution of dissolved organic matter in a typical plateau lake using end-member mixing analysis based on spectroscopic, stable isotope and molecular fingerprint - Yunxuan Cheng; Shasha Liu; Rui Fu; Yi Ren; Yuxuan Zhang; Ziwen Yin; Fengchang Wu (Journal of Hydrology, 2026)

Mechanical response of layered heterogeneous hydrate-bearing sediments to depressurization - Hua Du; Huie Chen; Fansheng Kong; Qing Wang; Yonggui Luo; Xiang Gao; Jinzhong Zhu; Lanting Fu; Rui Fu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Sodium fluoride assisted sulfate leaching of oxidized copper ores - Youchuan Chen; Xinzhuang Fu; Rui He; Chuanxi Peng; Wenjun Fu; Di Chen; Chen Zhang; Tong Yue (Hydrometallurgy, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Experimental investigation of the gas desorption–diffusion behavior of multi-scale outburst-prone coal under constant desorption pressures - Chaojun Fan; Rui Zhu; Lei Yang; Mingkun Luo; Xiang Fu; Xuan Liu; Xiaofeng Jiang (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Polysiloxane-enabled dual-interphase engineering coupled with fluorescence diagnosis of Ni2+ dissolution for 4.6 V lithium metal batteries - Hankun Zhang; Jiacheng Yan; Benhua Wang; Jinqiang Gao; Chao Fu; Rui Zhang; Xiaowei Huang; Xiaowei Tang; Zhengzhao Yang; Kefei Wang; Bowei Ju; Xiangzhi Song; et al. (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Robust identification of known and unknown weeds with crop center localization based on Open-set object detection - Lamin L. Janneh; Leilei He; Bryan Gilbert Murengam; Xiaojuan Liu; Mbemba Hydara; Man Xia; Rui Li; Yanxin Zhang; Longsheng Fu (Precision Agriculture, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Occlusion-aware pinching point positioning using shoot morphology for robotic summer pruning of kiwifruit - Bryan Gilbert Murengami; Leilei He; Shuolin Kong; Lamin L. Janneh; Xiaojuan Liu; Wenhao Guo; Rui Li; Jinyong Chen; Spyros Fountas; Hin Lim Shen; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Binocular-depth-guided dual-view camera-LiDAR fusion for kiwifruit pose estimation in robotic harvesting - Shiao Niu; Leilei He; Qilin Gong; Qichen Huang; Ruichao Luo; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Anastasia Grecheneva; et al. (Computers and Electronics in Agriculture, 2026)

Propylparaben exposure may impair uterine decidualization via FDX1 downregulation and induce preeclampsia-like symptoms in mice - Xiaohui Li; Rui Fu; Huiyu Liu; Yuhan Cai; Cong Zhang (Reproductive Toxicology, 2026)

First early Toarcian B/Ga paleosalinity record from the eastern Tethyan Ocean: Implications for hydroclimate evolution - Ying Nie; Wei Wei; Yansheng Shan; Shengqiang Zeng; Shuai Zhang; Ahmed Mansour; Rui Wang; Jianguo Yin; Shouji Pang; Fanyang Meng; Shiming Dong; Weihong Pan; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Occurrence and leaching of per- and polyfluoroalkyl substances in waste incineration residues: Insights into thermodynamic mechanisms and implications for environmental release - Lanlan Fu; Xingyao Huang; Xuemei Liu; Nan Zhang; Rui Ma; Xinyue Wang; Yue Zhi; Lin Li; Xiaoming Wang (Journal of Hazardous Materials, 2026)

Indole inhibits anaerobic digestion by disrupting AHLs-mediated quorum sensing - Dongxue Lu; Boyang Chen; Erqi Nie; Shujuan Lian; Rui Li; Rongbo Guo; Shanfei Fu (Journal of Hazardous Materials, 2026)

Genesis of boltwoodite in the hinterland surface of the Taklamakan Desert: Implication for exploration of sandstone-hosted uranium deposits - Liqun Wu; Shouyu Wang; Yangquan Jiao; Gui Wang; Liang Yue; Zhenpeng Tao; Wenlong Yang; Rui Chu; Mingzheng Zhang; Yingli Fu; Bingqian Li (Journal of Geochemical Exploration, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Enhanced SMA friction self-restoring damper (eSMA-FSRD) with leveraged force-displacement control for structural seismic resilience - Maojun Yuan; Lueqin Xu; Rui Jiang; Da Fu; Wei Guo (Engineering Structures, 2026)

Microwave-assisted synthesis of FeN Co-doped ZIF-8 derived carbon for low-concentration lithium recovery via CDI: Adsorption performance and mechanism - Yongsi Xie; Jiemei Fu; Chunxue Li; Juan Luo; Rui Ma; Shichang Sun (Desalination, 2026)

Low-cost and compact spring-type origami triboelectric nanogenerator for human kinetic energy harvesting and intelligent motion interaction - Zhelin Jin; Jie Cao; Rui Lei; Xu Han; Xianpeng Fu; Guoxu Liu; Haisheng Liu; Guanggui Cheng; Jianning Ding (Chemical Engineering Journal, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Fracture development characteristics in carbonate reservoirs: insights from stress field simulation with a heterogeneous rock mechanics model and adaptive boundaries - Yao Wang; Wenlong Ding; Zhongliang Guo; Chenggang Li; Bochao Tang; Ziyou Zhang; Dong Fu; Rui Xia (Carbonates and Evaporites, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Optimal basal-to-topdressing nitrogen ratios promote soil c-n coupling through microbial community modulation across loam and clay loam soils of North China Plain cropland - Jingyu Li; Yanqun Wang; Bin Wang; Rui Hou; Wenchao Zhen; Yuanyuan Huang; Yufei Liu; Xuguang Li; Zhengping Peng; Xin Fu (Applied Soil Ecology, 2026)

Rapid assembly of structurally diverse 3,4-dihydroquinazolines with anticancer activity via SDS-promoted aqueous synthesis - Fu-Qiang Yu; Pei-Lu Song; Yan-Rui Fan; Jun-Wei Wang; Xu-Jie Wang; Jin-Fei Yang (Molecular Diversity, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Retraction notice to “Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period” [Sci. Total Environ. 906 (2024) 167622] - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2026)

Hierarchical regulation and molecular functions of co-transcriptional splicing - Rui Niu; Aiming Zhang; Michael G. Rosenfeld; Xiang-Dong Fu; Yajing Hao (Science Bulletin, 2026)

Long-term changes in spatio-temporal heterogeneities of vegetation greenness and land surface temperature in China - Rui Yao; Yongjie Li; Tingting Ma; Minfeng Yuan; Zhihao Zhang; Siyuan Chen; Chuan Wang; Binghan Wang; Zhenyu Fu; Hengwei Li (Remote Sensing Applications: Society and Environment, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Enhancement of microbial protein production via hydrogen oxidizing bacteria in microbial electrolytic protein-production cell system - Rui Dong; Hangyu Sun; Yilin Jiang; Haotian Liu; Yue Wang; Xingjia Fu; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

The relationship between problematic social network use and network collaborative learning among vocational college students: the chain-mediated role of cognitive curiosity and digital literacy - Rui Li; Wangqian Fu; Yuqian Liang; Yuanmeng Zhao; Peng Peng (Cognitive Processing, 2026)

Form-associated quality variation and exploratory transcriptome-metabolome characteristics in selected Gastrodia elata tuber samples - Rui Yang; Fu-Lai Luo; Ping Wen (Plant Biotechnology Reports, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Preparation and characterisation of two new malonylated rare ginsenosides by acid hydrolysis and their anti-hepatoma activities - Ya-Qian Lu; Xiao-Man Jin; Fu-Rui Zhang; Mei-Hui Li; Wen-Wen Li; Wei Li; Chun-Su Yuan; Zhi Liu (Natural Product Research, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Multi-water source mixing controls transformation of dissolved organic matter in a coastal intertidal zone - Ying Liang; Xulong Gong; Rui Ma; Qinglong Fu; Xue Jiang; Kaige Ma; Yuan Liu; Ziyong Sun (Journal of Hydrology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Ascosphaeraapis LncRNA6140 promotes the infection of honeybee larvae through the milR5658-x–ATPase axis - Jianfeng Qiu; Tao Wu; Shuai zhou; Nian Fan; Genchao Gan; Zhitan Liu; Zhongmin Fu; Rui Guo; Dafu Chen (Insect Biochemistry and Molecular Biology, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Underestimation of industrial contributions to VOC fluctuation in the Hangzhou Bay: Insights from simultaneous measurements and ML-SHAP analysis - Kun Hu; Song Guo; Lei Shen; Zichao Wan; Xinshi Ni; Rui Tan; Xudong Tian; Bingye Xu; Limin Zeng; Qingyan Fu; Min Hu; Sihua Lu (Environmental Pollution, 2026)

Spatiotemporal heterogeneity in the association between surface ozone and wheat yield across China: A phenological analysis - Tianning Zhang; Yuanyuan Li; Xinxin Li; Rui Wang; Kaiyue Wei; Haijiang Kong; Huan Liu; Hongquan Song; Yongze Song; Shenglei Fu (European Journal of Agronomy, 2026)

Control of zeolite local microenvironment by organofluorination engineering toward efficient c-C4F8/C3F8 separation - Rui Sun; Zicheng Wan; Yaqi Wu; Yaohan Fu; Yang Zhang; Chenyang Yang; Heng Zhao; Ziqi Tian; Liang Chen (Chemical Engineering Journal, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

Statistical optimization of fungal chitosan production by Aspergillus niger using agro-industrial residues - Fengwei Yin; Jie Huang; Rui Wang; Yao Chen; Xiaolong Sun; Yongqian Fu (Biocatalysis and Agricultural Biotechnology, 2026)

Enhancing the spatio-temporal resolution of urban PM2.5 mapping via large-scale mobile monitoring data and machine learning - Rui Xu; Dawen Yao; Ruhui Cao; Yixin Fu; Ting Gan; Yonghong Liu (Atmospheric Pollution Research, 2026)

Hyperspectral model for evaluating nitrogen requirements of high-quality indica fragrant rice in South China using the critical nitrogen concentration dilution curve - Yufen Zhang; Feifei Zhu; Zhaowen Mo; Kaiming Liang; Zhanhua Lu; Yibo Chen; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Xinyu Wang; Songpo Duan; et al. (Plant and Soil, 2026)

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Biophotocatalytic and bioelectrocatalytic strategies for methane production and oxidation: emerging pathways and perspectives - Zhenni Cheng; Xiaolei Fan; Rui Li; Kangqing Fei; Rongbo Guo; Shanfei Fu (Archives of Microbiology, 2026)

Hyperallometric Fecundity and Size-Dependent Egg Provisioning in the Yellowfin Goby (Acanthogobius flavimanus), a Short-Lived Estuarine Fish - Yupin Pu; Rui Ma; Hao Shi; Guanghui Fu (Fishes, 2026)
In highly variable estuarine environments, short-lived fishes must balance immediate reproduction against future growth, yet the reproductive role of maternal size remains poorly resolved. Here, we analyzed biological surveys of the yellowfin goby Acanthogobius flavimanus from Haizhou Bay, Yellow Sea, collected between 2023 and 2025, combining fecundity estimation, egg morphometry, histology, and size-structured reproductive-output modeling. Absolute fecundity scaled hyperallometrically with total length (β = 3.18, 95% CI: 3.05–3.31, R2 = 0.71, p 180 mm total length represented only 4.8% of abundance but contributed 18.5% of total standardized egg-production output under the assumptions of the model. Inter-annual monitoring further indicated a decline in mean body size and in the proportion of large individuals from 2023 to 2025, a pattern consistent with size truncation but requiring longer-term monitoring for causal attribution. These findings suggest that large females can contribute disproportionately to reproductive output even in a short-lived estuarine fish and support the inclusion of size structure in fisheries assessment and management.

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Accessory minerals constrain anatexis and melt extraction in deep crust and implications for granite genesis - Wenxiang Zhang; Yujie Zhao; Bin Fu; Guangyan Zhou; Hao Wang; Rui Li; Zhaochu Hu; Yuanbao Wu (Geochimica et Cosmochimica Acta, 2026)

Design and crashworthiness of a modular discrete re-entrant auxetic honeycomb - Ye Fu; Yilin Zhu; Xue Rui; Shengdong Zhao; Longtao Xie; Chuanzeng Zhang (Engineering Structures, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Corrigendum to “The nanocellulose fiber scaffold to construct a hierarchical phenolic coating on cotton fiber surfaces for inactivating pathogens through an enhanced protein adsorption mechanism” [Carbohydrate Polymers 348 (2025) 122821] - Liwen Shen; Rui Cai; Feiyang Zhao; Jingjing Jiang; Jiajia Fu; Feiya Fu; Hongyan Diao; Xiangdong Liu (Carbohydrate Polymers, 2026)

Efficacy and Safety of Intravenous Thrombolysis with Tenecteplase in Patients with Wake-Up Branch Atheromatous Disease - Lili Zhu; Ying Zhang; Jiarong Li; Liang Song; Haoran Li; Yang Yang; Lijuan Liu; Shaolei Zhang; Xiaofei Gao; Weifeng Chen; Guo Rui; Haiqiang Qin; et al. (Translational Stroke Research, 2026)
Branch atheromatous disease (BAD), a subtype of acute ischemic stroke (AIS), is associated with a high risk of early neurological deterioration (END) and poor prognosis. Wake-up stroke (WUS), comprising 20%–30% of AIS cases, is typically excluded from thrombolysis because of unknown onset time. Using diffusion-weighted imaging/fluid-attenuated inversion recovery (DWI/FLAIR) mismatch, we evaluated the efficacy and safety of Tenecteplase (TNK) thrombolysis in patients with BAD-related WUS. We retrospectively recruited 1,062 patients from seven Zhengzhou hospitals between January 2021 and June 2025. The patients received either TNK (n = 338) or dual antiplatelet therapy (n = 724). Propensity score matching (PSM; 1:1, caliper 0.02) yielded 292 matched pairs. Early neurological changes were evaluated using the National Institutes of Health Stroke Scale (NIHSS), and 90-day outcomes were evaluated using the modified Rankin Scale (mRS). After PSM, TNK significantly reduced the risk of END (odds ratio [OR] = 0.425, 95% confidence interval [CI]: 0.262–0.689; P < 0.001). Patients treated with TNK were more likely to achieve good functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) with fewer poor outcomes (mRS ≥ 4). There were no significant differences in symptomatic intracranial hemorrhage, other bleeding events, or mortality among the groups. DWI/FLAIR mismatch-guided TNK thrombolysis appears to overcome the limitations of an unknown onset time in WUS and may counteract the progressive pathophysiology of BAD. TNK intravenous thrombolysis may be a safe and effective treatment for patients with wake-up BAD and DWI/FLAIR mismatches.

An intelligent lithofacies identification method for tight carbonate reservoirs integrating dynamic clustering and BiLSTM-attention network - Guangjie Fu; Zihao Mu; Haiwei Mu; Rui Yang; Meiqi Jia; Xinyu Li (Earth Science Informatics, 2026)

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Volatile metabolomics and Metaproteomics reveal key flavor formation mechanisms in mixed-culture fermented Rice slurry - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Research International, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

A combination of QTL mapping and genome‑wide association study revealed key genes for heat tolerance in maize - Xining Jin; Hangdan Qu; Pingxi Wang; Huaisheng Zhang; Tiantian Li; Xiangyuan Wu; Shilin Chen; Yaqiu Zhao; Fei Wang; Rui Song; Zhiyuan Fu; Xiaoxiang Zhang (Theoretical and Applied Genetics, 2026)

What are the driving factors and spatial-temporal characteristics of the landscape ecological risk of the Yellow River Delta? - Yao Zhang; Rui Hu; Tian Li; Zehao Zhang; Zhanyong Fu; Kaikai Dong; Jinzhao Ma; Zhaohua Lu; Jingkuan Sun (Environment, Development and Sustainability, 2026)

Analysis of Vortex-Induced Vibrations in a Test Production Riser Subjected to Internal Multiphase Flow - Qiang Fu; Liangjie Mao; Yu Chen; Rui Qin; Junlong Zhu (Journal of Marine Science and Engineering, 2026)
The natural gas hydrate production riser is the main passage for offshore hydrate production and transport. Its safe operation directly affects the production process. However, current hydrate production methods cannot avoid hydrate decomposition and formation inside the pipe. Hydrate phase change causes internal multiphase flow. Together with the external ocean current, it leads to more complex nonlinear vibration of the riser. Based on China’s gas hydrate trial production in the Shenhu area of the South China Sea, this study establishes a dynamic model of a production riser. The model considers hydrate phase change inside the pipe and vortex-induced vibration. It is solved using the Newmark-β method, and its validity is confirmed by CFD simulations. The results show that, under the combined action of ocean currents and internal multiphase flow, the riser exhibits a clear multi-frequency response in vortex-induced vibration. Its spatial trajectory is highly irregular. Specifically, hydrate phase change increases internal gas content and gas slippage, elevating fluid velocity. This reduces the riser’s structural stiffness and effective tension, altering the VIV response. In addition, lower top tension and higher slurry density, flow rate, and outlet backpressure delay hydrate decomposition. These factors also reduce the effective tension along the riser and increase its in-line deformation.

Prediction and application of water inrush in water-rich area of TBM construction deep buried tunnel - Fa-yong Gao; Kun Yang; Yan-qiang Cheng; Yong-tao Ma; Kang Fu; Ming-yang Tang; Jin-rui Duan (Applied Geophysics, 2026)

The Role of Metal Ions in Mitochondria: From Energy Metabolism to Cell Destiny - Chunlan Li; Hongpeng Liu; Qiuyue Mao; Jing Fu; Yu Yin; Lijuan Zhu; Kunrong Li; Rui Li; Pengyue Zhang (Biological Trace Element Research, 2026)

Corrigendum to “Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling” [Tissue and Cell, 97 (2025) 103089] - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2026)

Corrigendum to “Targeted amplicon sequencing facilitated a novel risk assessment framework for assessing the prevalence of broad spectrum bacterial and coronavirus diseases” [Sci. Total Environ. 912, (2024) 168797] - Songzhe Fu; Haifeng Li; Rui Wang; Yixiang Zhang; Ziqiang Zhang (Science of The Total Environment, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Simultaneous exposure to avermectin enhances the toxicity of R-dinotefuran and reduces the toxicity of S-dinotefuran - Zongqi Hu; Caihao Mou; Rui Wang; Yixiang Wang; Shitao Hu; Lili Fu; Quan Zhang (Journal of Environmental Sciences, 2026)

Toward energy-efficient recycling of spent LiFePO4 cathode: Lowering reduction temperature though bamboo-assisted pyrolysis and sodium carbonate-mediated in-situ mineralization - Rui Diao; Cunzhang Yang; Liting Fu; Xinran Zhou; Bowen Li; Yakai Ma; Zhenting Zha; Fenglei Qi; Xiaohao Liu; Peiyong Ma (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Time-dependent dynamics of starch structure, functionality and quality in rice noodles during inoculated fermentation - Yuanyuan Ren; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Carbohydrate Polymers, 2026)

Hybrid crested porcupine optimizer decomposition method and deep neural network to predict long-term rainfall - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu (Theoretical and Applied Climatology, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Unpacking asthma risks: A multi-level spatial analysis of social determinants of health in the U.S. - Ming Yan; Cong Fu; Xiao Huang; Siqin Wang; Yuchen Li; Lambed Tatah; Rui Zhu; Yanqing Xu (Applied Geography, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Multi-Feature and Multi-Step Monthly Rainfall Forecasting with the Hybrid VMD-LSTM-CATNet Model in Diverse Climatic Regions - Man-Hong Fan; Xiao-Ying Ma; Shi-Qi Xu; Rui-Lin Fu; Zhong-Xing Tao (Water Resources Management, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

In situ Temperature Monitoring in a Large Scale Artificial Ground Freezing Project - Yongkui Fu; Rui Liu; Xiaofei Yang; Guohui Huang; Junwei Wang; Song Zhang (Geotechnical and Geological Engineering, 2026)

A novel electrostatic-assisted airflow pollination end-effector for kiwifruit flowers with optimized charging and spraying parameters - Yusong Ding; Leilei He; Juncai Huang; Xin Wei; Yufei Shi; Hin Lim; Spyros Fountas; Shaojin Wang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Nationwide occurrence and flux estimates of PFAS in leachate from waste-to-energy sector: an emerging reservoir linked to short-term waste storage - Xinyue Wang; Fan Chen; Yue Sun; Lanlan Fu; Rui Ma; Yue Zhi; Qian Wang; Xiaoming Wang (Water Research, 2026)

Identification of novel B-cell neutralizing epitopes in goose Astrovirus type 2 - Shichao Yuan; Rui Fu; Bangfeng Xu; Wenqing Wang; Huamao Ding; Xue Pan; Chunxiu Yuan; Qinfang Liu; Zhifei Zhang; Qiaoyang Teng; Xiaona Shi; Minghao Yan; et al. (Veterinary Microbiology, 2026)

Earthworm pretreatment enhances anaerobic biogas production through time-dependent structural modification of coal - Yunxia Niu; Daping Xia; Xiao Zhou; Bin Xu; Huizhen Chang; Kuo Jian; Rui Luo; Zhijia Yu; Haijiao Fu (Journal of Environmental Chemical Engineering, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Miocene carbonate crash in the eastern Pacific: A catalyst for early rare earth element enrichment - Yayue Tang; Dengfeng Li; Fei Huang; Rui Wang; Jiewei Hu; Jinzhou Peng; Yu Fu; Xiaoming Sun (Global and Planetary Change, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Interfacial proton transfer in MOF-functionalized aerogel enabling for selective heavy metal adsorption - Jun-Heng Fu; Baihang Cai; Yeshuang Zhong; Xinru Gong; Shuangfeng Fang; Fei Wang; Yufeng Yan; Rui Dai; Puyuan Liu; Jianye Gao; Ruihan Wang; Ying Cao; et al. (Desalination, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Characterization and influencing factors of hydroxymethanesulfonate (HMS) in the North China plain: integration of field measurements and theoretical calculations - Chun Chen; Haijie Zhang; Yele Sun; Junling Li; Zhiqiang Zhang; Jian Gao; Rui Gao; Lianfang Wei; Nan Ma; Wanyun Xu; Pingqing Fu (Atmospheric Environment, 2026)

Spatiotemporal modeling of oxygen transport and layered regulation in tidal flow constructed wetlands - Rui Ma; Lanlan Fu; Jiangsen Ma; Lei Jiang; Yiyuan Zhuo; Linsong Cheng; Fangying Ji; Xiaoming Wang (Water Research, 2026)

Bacterial transport enhancement by colloidal gas aphrons in heterogeneous aquifers: Performance evaluation and mechanistic insights - Yufeng Fu; Chuanyu Qin; Tingdi Zhang; Chengwu Zhang; Jintao Ru; Rui Tang (Water Research, 2026)

Carbon isotope stratigraphy of the Doushantuo Formation in basinal facies of South China: Constraints on the Shuram excursion in a deep ocean environment - Rui Fu; Chaochao Xing; Lei Zhang; Meng Ning; Fangbing Li; Xianguo Lang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Zoning-grading optimization of watershed ecological security network integrating function and structure: A case study in the Three Gorges Reservoir Area - Dan Chen; Kai-rui Guo; Wei Zeng; Fu-hai Wang (Journal of Cleaner Production, 2026)

A novel multi-scale structural equivalent method for jointed rock masses and its application to slope stability analysis - Jia Wang; Wen Zhang; Han Yin; Rui Fu; Qi Sun; Jiali Han; Junqi Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Malt endogenous amylase-hydrolyzed nanostarch for anthocyanin encapsulation by nanoprecipitation: Fabrication, characterization and evaluation - Shucheng Liu; Yanyun Lin; Xiaoyan Fu; Qiuyu Xia; Naiyong Xiao; Yang Liu; Rui Hai Liu; Wen Xia (Food Chemistry, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Response of offshore wind turbine tripod suction bucket foundation under wind and multi-directional seismic loading conditions - Dingtao Yan; Rui Liu; Yue Yan; Dengfeng Fu; Dong Wang (Computers and Geotechnics, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Brown Adipose Tissue Activation Alleviates Cerebral Ischemia–Reperfusion Injury by Increasing 14–3-3ζ Secretion from Circulating Extracellular Vesicles to Suppress P53 Activity - Hui Yue; Xiaohua Wang; Yue Liu; Yinglian Zhou; Yifei Wang; Xuemei Zhang; Shan Huang; Changsi Ai; Jin Fu; Rui Wang (Molecular Neurobiology, 2026)

Mechanistic Investigation of TSPO-Mediated Dysregulation of Mitochondrial Copper Homeostasis in Microglia and its Role in Perioperative Neurocognitive Disorders - Youli Fu; Jiahe Lian; Yinglong Liu; Yongxin Liu; Zihan Xu; Haoran Fan; Yongliang Zhu; Yingxia Liang; Lina Sun; Rui Zhang (Molecular Neurobiology, 2026)

Development of an environmentally sustainable composite incorporating phosphogypsum aggregate: a perspective for enhancing interfacial stability - Shiyuan Fu; Chiqiu Wu; Wei Lv; Yuan Feng; Xue Liu; Yuxin Zhou; Kangning Liu; Rui Yu (Innovative Infrastructure Solutions, 2026)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Opportunities and challenges in the application of Digital Twins for orchard management - Xiaojuan Liu; Leilei He; Shiao Niu; Rui Li; Yaqoob Majeed; Xiaoxu Sun; Jinyong Chen; Xiaojuan Li; Kerry Brian Walsh; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Molecular-scale investigation on the role of MnO2–mediated oxidation in regulating photochemical reactivity of dissolved organic matter - Rui Chai; Huanxin Ma; Hengyi Fu; Ke Sun; Chunhua Feng; Chao Jin; Rongliang Qiu; Shishu Zhu (Water Research, 2025)

Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Numerical calculation of line heating for hull curved plate based on strain direct boundary - Shun Wang; Haohao Jia; Yuxuan Fu; Ji Wang; Rui Li (Ocean Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Effects of representative Chinese cattle breeds on the eating quality and microstructure of braised beef - Jian Hu; Xiaoke Fu; Yijie Cai; Ronglan Wang; Rui Xu; Chengrong Zheng; Xing Chen; Bowen Yan (International Journal of Gastronomy and Food Science, 2025)

Deciphering microbial and metabolite dynamics in rice noodle fermentation: A metagenomic and untargeted metabolomic approach - Yuanyuan Ren; Yuhang Li; Yingjie Lei; Rui He; Jin Fu; Ding Ma; Geng Zhong (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Nano-thiophene-graphdiyne engineered buried interface toward homogeneous crystallization of perovskite films - Yutongyang Fu; Le Liu; Zhibin Yu; Rui Han; Yilin Chang; Yunxin Zhang; Wenfei Guo; Bin Huang; Jiajia Du; Wenfeng Yang; Tonggang Jiu (Chemical Engineering Journal, 2025)

Low-temperature microwave pyrolysis PVC to achieve modulation of elemental chlorine migration and conversion: performance evaluation of microwave absorption-catalysis-chlorine fixation trifunctional catalyst - Wenjun Fu; Juan Luo; Shichang Shun; Jiangyi Luo; Chengling Liu; Rui Ma (Chemical Engineering Journal, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Intensified rainfall overrides vegetation greening in driving erosion and carbon loss on the Tibetan Plateau - Rui Deng; Dongfeng Li; Yi Zhao; Desmond E. Walling; Panos Panagos; Pasquale Borrelli; Philippe Ciais; Yuefei Huang; Yuanyuan Bai; Sergey Chalov; Valentin N. Golosov; Xudong Fu; et al. (Science Bulletin, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Resorcinol-formaldehyde resin as co-catalyst in Fenton-like reaction: Synergistic enhancement of Fe3+/Fe2+ cycling via phenolic hydroxyl redox and conjugated-structure mediated electron transfer - Qingnan Meng; Rui Fu; Linzhi Huang; Zhangwen Xie; Yufei Tang; Kang Zhao (Journal of Cleaner Production, 2025)

Effects of fermentation by different strains on the Physico- chemical properties, quality, and metabolic profile of Rice noodles - Yuanyuan Ren; Yuhang Li; Rui He; Yingjie Lei; Yi Zhao; Zikuan Meng; Ding Ma; Jin Fu; Geng Zhong (Food Chemistry, 2025)

Preparation of stir bars coated with N-modified COFs and application to estrogen detection in dairy products - Xixi Lian; Lianzhi Wang; Jianing Sun; Yingying Fu; Zhengchao Duan; Yazhuo Wang; Che Zhao; Gangqi Cheng; Rui Shan (Food Chemistry, 2025)

Study on the distribution characteristics and toxic risks of trace elements in the eggs of green turtles (Chelonia mydas) nesting on the Xisha Islands - Xiang Li; Li Jian; Minyu Fu; Henyi Zhang; Yuxin Zhang; Rui Guo; Jichao Wang (Environmental Research, 2025)

Strengthening and repair of non-uniformly corroded RC columns by ECC or CFRP jacketing: Bond performance evaluation - Deming Fang; Jin Huang; Chuanqing Fu; Zhengyu Zhu; Rusheng Qian; Xingjian Liu; Rui He (Engineering Structures, 2025)

A novel upcycling process of polystyrene wastes into benzaldehyde by catalyst-free laser flash depolymerization and in-line oxidation - Fu-Lu Chang; Lun Chen; Bin Hu; Fu-Rui Chen; Han Yang; Guang-Jian He (Chemical Engineering Journal, 2025)

Entropy-phase synergy enables stable and high-rate layered oxide cathodes for sodium-ion batteries - Xingyue Yang; Mengfei Du; Jiali Fu; Yi Yang; Zhuo Xiong; Weiyue Li; Liangzhi Li; Jianping Long; Rui Li; Jian Chen; Anjun Hu (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Cassiterite U–Pb ages from the Tin Islands, Indonesia, the southern end of the Southeast Asian tin province - Jie-Hua Yang; Rui-Zhong Hu; Mei-Fu Zhou; Bernd Lehmann; Jun-Hong Zhao; Jing-Hua Wu; Liang Liu; Wei Mao; Zheng-Teng Cui; Mega Fatimah Rosana (Mineralium Deposita, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Identification of a hypoxia-related gene signature associated with childhood asthma - Wenlie Chen; Yuanlu Huang; Li Lei; Rui Zhang; Li Fu; Jinwen Liao; Shaohua Wang; Zhenzhuang Zou (Genes & Genomics, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Row-based kiwifruit counting pipeline for smartphone-captured videos using fruit tracking and detection region adaptation guided by support-post - Jiwei Zhang; Liguo Jiang; Leilei He; Zhenchao Wu; Rui Li; Jinyong Chen; Xiaoxu Sun; Yunfei Xue; Anastasia Grecheneva; Spyros Fountas; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Evaluation of heavy metal accumulation and pollution in soils from the vanadium–titanium magnetite mining region in Panzhihua, China - Tingting Fu; Hao Song; Bin Yang; Rui Liu (Ore and Energy Resource Geology, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

Interfacial electron modulation of FeCo LDH@CoS heterojunction for efficient oxygen evolution reaction - Zhen Guan; Hengzhong Chen; Bin Chen; Lingchen Kong; Zhou Shi; Yu Zhong; Wenjie Li; Wencan Qian; Rui Zhang; Jiang Wu; Zaiguo Fu (Journal of Environmental Chemical Engineering, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Unveiling city-scale urban roadside charging piles capacity: Geospatial knowledge-assisted small object detection and SDG 7-driven planning - Qin Huang; Teng Zhong; Liangchen Zhou; Rui Zhu; Xiao Fu; Changchang Zhou; Min Chen; Guonian Lü (Sustainable Cities and Society, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Enhancing Mnammox-driven nutrient removal in manganese ore-based constructed wetlands: The electron-shuttling role of straw-released humus - Rui Ma; Yiyuan Zhuo; Jintao Lei; Lanlan Fu; Jiangsen Ma; Linsong Cheng; Fangying Ji; Xiaoming Wang (Chemical Engineering Journal, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Sequence of middle-lower Ordovician in Shunbei area of Tarim Basin, China, and its geological significance - Rui Xiong; Heng Fu; Yong Li; Caizhu Xie; Ronggang Wang; Shaoze Zhao; Chuan Xu; Chongyang Xiao (Carbonates and Evaporites, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

PED-TRFIA: PEDV early on-site detection based on the time-resolved fluorescence ImmunoAssay - Bin Wang; Hongli Li; Rui Liang; Tingting Fu; Shusen Ji; Boya Li; Peichen Zhang; Haiyang Wu; Wenting Wang; Lianmei Bai; Xiuju Yu; Wei Hou; et al. (Analytica Chimica Acta, 2025)

Intelligent Alignment Control for Floating Raft Air Spring Mounting System Under Coupled Hull–Raft Deformation - Jian-Wei Cheng; Wen-Jun Bu; Ze-Chao Hu; Jun-Qiang Fu; Hong-Rui Zhang; Liang Shi (Journal of Marine Science and Engineering, 2025)
Shaft alignment is adversely affected by the increasingly severe coupled hull–raft deformation in deep-diving, highly integrated submersibles, thereby compromising operational safety and potentially amplifying vibration noise. To address to this issue, this paper investigates an intelligent alignment control method for the floating raft air spring mounting system (ASMS) applied to marine propulsion unit (MPU) under coupled hull–raft deformation conditions. A multi-objective alignment control algorithm was developed based on the NSGA-II optimization method within an N-step receding horizon optimal control framework, enabling simultaneous achievement of shaft alignment attitude adjustment, hull deformation compensation, raft deformation suppression, and pneumatic energy consumption. Experimental validation was conducted on two distinct ASMS prototypes to evaluate the control algorithm. Tests performed on the ASMS for MPU (MPU-ASMS) prototype demonstrated effective compensation of hull-induced deformations, maintaining shaft alignment offsets within ±0.3 mm and angularities within ±0.5 mm/m. Concurrently, experiments on the floating raft ASMS for the stern compartment (SC-FR-ASMS) achieved precise control of axial offsets within ±0.3 mm, angularities within ±0.5 mm/m, and vertical displacements of critical monitoring points within ±1 mm. The adaptive control strategy additionally proved effective in suppressing raft deformation while simultaneously optimizing pneumatic energy consumption. This research provides robust theoretical and technical foundations for intelligent vibration isolation systems in deep-sea equipment to accommodate extreme-depth-induced hull deformation and large-scale raft deformation.

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Shelter efficiency of windbreak influenced by stand configuration - Ruijie Zhang; Rui Ma; Yanjun Ma; Fu Zhang; Linyuan Wei; Gazangzhuoma Xie (Biosystems Engineering, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

A new benzoquinone and a new dihydroflavone from Fissistigma polyanthum and their bioactivity - Jian-Fen Xiao; Ming-Rui Yang; Pin-Xiang Fu; Rui Yang; Hong-Ping He; Hua-Yi Jiang (Phytochemistry Letters, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Deciphering the molecular mechanisms of oil palm lipid metabolism through combined metabolomics and transcriptomics - Jerome Jeyakumar John Martin; Wen Xu; Xinyu Li; Xiaoyu Liu; Lixia Zhou; Rui Li; Dengqiang Fu; Qihong Li; Hongxing Cao (Food Chemistry, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Origin of the giant Devonian Daxigou sedimentary siderite deposit, Central China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Rui-Zhong Hu; Zerui Ray Liu; Yanfeng Zhao (Mineralium Deposita, 2025)

CircNFIX promotes stemness and evasion of phagocytosis in glioma stem cells by sponging miR-449a to upregulate the expression of CD47 - Yuanwei Fu; Zhizhao Qu; Rui Bai; Liu Yang; Hongqin Wang (Molecular & Cellular Toxicology, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

An improved direct analysis method of transmission towers incorporating geometric defects and bolt slippage effects - Yu Zhu; Hong-Nan Li; Xing Fu; Jia-Xiang Li; Rui-Zeng Wei (Engineering Structures, 2025)

Flash elimination of nano-/microplastics from complex matrices with record efficiency and sustainability - Nuan Liu; Yingxin Ji; Feng Tang; Jianxin Fu; Chuntian Qiu; Rui Wang; Zhiyang Zhang; Lingxin Chen; Guoqing Wang (Chemical Engineering Journal, 2025)

Biochar mitigates greenhouse gas emissions from bulk soil in wheat-corn rotation system by inhibiting biochemical decomposition - Debo He; Rui Yang; Yan Fu; Dongni Hu; Han Ma; Xiaoguo Wang; Zhixin Dong; Bo Zhu (Agriculture, Ecosystems & Environment, 2025)

How Does Climate Change Influence the Regional Ecological–Social Risks of Harmful Dinoflagellates? A Predictive Study of China's Coastal Waters - Shangke Su; Zhaohe Luo; Jianhua Kang; Xinyuan Guo; Changyou Wang; Rui Jin; Jianguo Du; Xinqing Zheng; Kieng Soon Hii; Shifeng Fu; Wenjia Hu; Bin Chen (Global Change Biology, 2025)
Harmful dinoflagellates are widely distributed in coastal waters worldwide, posing multiple ecological and socioeconomic threats. Climate change may alter the biogeography of these species; however, few studies have linked shifts in harmful dinoflagellates' ecological distribution to their socioeconomic impacts. This study developed a framework to assess the spatiotemporal ecological–social risks posed by harmful dinoflagellates, identifying these algae as risk sources and considering mariculture and coastal populations as the primary risk receptors. China is the world's largest mariculture producer, with approximately 600 million residents living in coastal areas. Focusing on 14 key harmful dinoflagellate species in Chinese coastal waters, we evaluated ecological–social risks under present conditions and two projected climate scenarios for 2100. Our findings indicate that climate change may lead to reductions in suitable habitats for harmful dinoflagellates in tropical and subtropical regions, while habitats in higher‐latitude areas are likely to remain stable or expand. Risk area expansion is projected for four species and increased average risk intensity for three, with two species experiencing both. Nationally, total risk area is projected to remain stable, while cumulative risk intensity may decline by 16.64%. Regionally, risk intensity is expected to rise in northern provinces (up to 30.46%) and decline across most southern provinces. Importantly, we reveal a potential spatial “decoupling” of risk sources and receptors along the coast of China in the future. This decoupling demonstrates a reduced overlap between harmful dinoflagellate distributions and areas with dense mariculture or populations. Our findings suggest that, contrary to the common assumption that climate change universally exacerbates harmful algal impacts, these effects may vary across regions and species, highlighting the importance of localized adaptation strategies in risk assessment. This study provides a robust tool for understanding harmful dinoflagellate risks under climate change, thereby supporting the sustainable management of coastal ecosystems.

Optimization Control of Flexible Power Supply System Applied to Offshore Wind–Solar Coupled Hydrogen Production - Lishan Ma; Rui Dong; Qiang Fu; Chunjie Wang; Xingmin Li (Journal of Marine Science and Engineering, 2025)
The inherent randomness and intermittency of offshore renewable energy sources, such as wind and solar power, pose significant challenges to the stable and secure operation of the power grid. These fluctuations directly affect the performance of grid-connected systems, particularly in terms of harmonic distortion and load response. This paper addresses these challenges by proposing a novel harmonic control strategy and load response optimization approach. An integrated three-winding transformer filter is designed to mitigate high-frequency harmonics, and a control strategy based on converter-side current feedback is implemented to enhance system stability. Furthermore, a hybrid PI-VPI control scheme, combined with feedback filtering, is employed to improve the system’s transient recovery capability under fluctuating load and generation conditions. Experimental results demonstrate that the proposed control algorithm, based on a transformer-oriented model, effectively suppresses low-order harmonic currents. In addition, the system exhibits strong anti-interference performance during sudden voltage and power variations, providing a reliable foundation for the modulation and optimization of offshore wind–solar coupled hydrogen production power supply systems.

Preparation and Characterization of Diclofenac Sodium-Purolite A430MR Complexes for Taste Masking - Genyang Ye; Qun Wang; Yibo Shang; Yibo Li; Rui Yang; Boyu Jing; Qiang Fu (AAPS PharmSciTech, 2025)

Frequent horizontal transfer of AHPND-related plasmid among Vibrionaceae in the rotifers and its implication for shrimp disease management - Songzhe Fu; Ziqiang Zhang; Wenyu Zhao; Rui Wang; Junfeng Hui; Qian Yang (Aquaculture, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

Enhanced immobilization of Cd(II) by successive isomorphic substitution with Ca(II) and Mg(II) from ternary layered double hydroxides - Xiaoxian Zhang; Junnan Rui; Shuyi Yang; Rongbing Fu; Yuping Qiu (Journal of Hazardous Materials, 2025)

Superior properties of biochar contribute to soil carbon sequestration and climate change mitigation - Debo He; Rui Yang; Yan Fu; Bo Zhu (Journal of Environmental Chemical Engineering, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Inorganic arsenic in aquatic products in Shenzhen, China from 2018 to 2024: Levels, temporal variation and health risk assessment - Bo Fu; Kai Lin; Sisi Yu; Yiming Ge; Xinjie Li; Wenchao Zhu; Lei Tan; Rui Wang; Jixi Ou; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Reversing anther thermotolerance by manipulating the cis-elements in the promoter of a high-temperature upregulated gene Casein Kinase I in upland cotton - Yanlong Li; Yinuo Fu; Yaoyao Li; Rui Zhang; Jing Yang; Huanhuan Ma; Ling Min; Xianlong Zhang (Science China Life Sciences, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Modeling and Quantitative Assessment of Critical Defects in Shield Tunnels with Cascading Effects - Xiangyu Chang; Rui Zhang; Jianxiao Mao; Yuguang Fu; Hongyun Fan; Hao Wang (Geotechnical and Geological Engineering, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Synergistic reduction of pollutants and GHGs in China's PET industry: A material metabolism perspective - Fu Guo; Rui Li; Yifan Gu; Mingxuan Tuo; Zixin Bian; Yihan Li; Qingbin Yuan; Ming Yang; Yufeng Wu (Resources, Conservation and Recycling, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Facile and scalable synthesis of bio-based adsorbents from tannin for economical uranium extraction from seawater - Xingyu Fu; Minsi Shi; Dingyang Chen; Zixu Ren; Qing Bai; Rui Zhao (Desalination, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Advancements in artificial pollination of crops: from manual to autonomous - Leilei He; Xiaojuan Liu; Yusong Ding; Xudong Jing; Haojie Dang; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Spyros Fountas; Jayme Garcia Arnal Barbedo; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Selective anti-proliferative lignans towards TNBC cells from Knema elegans (Myristicaceae) - Zhen Peng; Xin Han; Zhao Lu; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Kinetics and mechanism study for the UVB-LED chlorination of veterinary antibiotic-sulfamonomethoxine - Yunhao Fu; Yanbo Zhai; Rui Qin; Zuo Tong How (Journal of Water Process Engineering, 2025)

Enhanced effects and mechanisms of Tween80 on aniline biodegradation by newly isolated Pseudomonas veronii T1 - Yufeng Fu; Tingdi Zhang; Chuanyu Qin; Chengwu Zhang; Jintao Ru; Rui Tang; Guoxin Huang; Jian Chen (Journal of Environmental Chemical Engineering, 2025)

Physical modification of cassava starch by alternating magnetic field treatment: Effects on fine structure, retrogradation and in vitro digestibility - Rui He; Jinyu Du; Aiguo Feng; Jie Zhang; Geng Zhong; Naifang Fu; Tao Yang (Food Chemistry, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Variability in maternal transfer efficiency of trace elements in green turtles (Chelonia mydas) - Li Jian; Xiang Li; Xiaobo Zheng; Henyi Zhang; Minyu Fu; Rui Guo; Jichao Wang (Environmental Pollution, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Ce-doped TiO2 supported RuO2 as efficient catalysts for the oxidation of HCl to Cl2 - Jiahui Liu; Fangyuan Dong; Yaqi Huang; Yanghe Fu; Xinqing Lu; Rui Ma; Fumin Zhang; Shuhua Wang; Weidong Zhu (Journal of Environmental Sciences, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

Growth characteristics based multi-class kiwifruit bud detection with overlap-partitioning algorithm for robotic thinning - Haojie Dang; Leilei He; Yufei Shi; Lamin L. Janneh; Xiaojuan Liu; Chi Chen; Rui Li; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Xiaoxi Kou; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Diurnal and seasonal variation of surface heat island of local climate zones using FengYun-4A land surface temperature data - Longteng Fu; Xian-Xiang Li; Rui Xin; Min Min; Lixin Dong (Urban Climate, 2025)

Human cardiac organoid model reveals antibacterial triclocarban promotes myocardial hypertrophy by interfering with endothelial cell metabolism - Nana Yang; Jiahong Chen; Yujie Zhu; Wenxin Shan; Zheng Cao; Yiwen Fu; Huanhuan Cao; Yanyan Li; Yukun Xiang; Shusi Ding; Huiqing Wang; Yaobo Zhao; et al. (Science Bulletin, 2025)

Petrogenesis of the > 2.90 Ga komatiite in the Sujiagou region of the North China Craton: Implications for Archean mantle source and geodynamic setting - Rui Zuo; Xiaoping Long; Bin Wu; Mei-Fu Zhou (Precambrian Research, 2025)

Alkaloids from Dendrobium nobile and their anti-inflammatory activities - Zao-Yu Xu; Chao-Fan Wang; Wen Li; Nan Fu; Rui Zhan (Phytochemistry Letters, 2025)

Monitor and classify dough based on color image with deep learning - Bryan Gilbert Murengami; Xudong Jing; Hanhui Jiang; Xiaojuan Liu; Wulan Mao; Yuedan Li; Xueyong Chen; Shaojin Wang; Rui Li; Longsheng Fu (Journal of Food Engineering, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Enhancement of antibacterial activity of cinnamaldehyde against Bacillus cereus by nanoemulsion and its application in milk - Rui Cui; Fu-Yu Liu; Hong Wu (Food Bioscience, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Observed response of microwave land surface emissivity to antecedent rainfall in Hainan Island - Jiawei Duan; Yuyun Fu; Jiheng Hu; Rui Li (International Journal of Remote Sensing, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

The nanocellulose fiber scaffold to construct a hierarchical phenolic coating on cotton fiber surfaces for inactivating pathogens through an enhanced protein adsorption mechanism - Liwen Shen; Rui Cai; Feiyang Zhao; Jingjing Jiang; Jiajia Fu; Feiya Fu; Hongyan Diao; Xiangdong Liu (Carbohydrate Polymers, 2025)

Failure mechanism of toppling in anti-dip layered rock slope: a case study of the Xiangpingshan landslide in southwest China - Changkui Wang; Leilei Jin; Wenxi Fu; Fei Ye; Rui Qian; Guangchao Lv; Shuang Yao (Bulletin of Engineering Geology and the Environment, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Life cycle assessment of hydrogenotrophic denitrification in membrane aerated biofilm reactors for sustainable wastewater treatment - Rui Li; Ming-yi Lu; Rong-bo Guo; Haoran Duan; Bing-jie Ni; Shan-fei Fu (Water Research, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Constraints of in-situ elemental compositions and U–Pb ages of cassiterite on the origin of the Cretaceous Gejiu and Dulong tin deposits, SW China: Implications for the linkage of tin belts in SE Asia - Zhi Zhang; Jie-Hua Yang; Rui-Zhong Hu; Bin Fu; Qian Hu; Mei-Fu Zhou (Lithos, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Deciphering the biodegradation mechanism of 3,6-dichlorocarbazole using a novel isolate for its implication in bioaugmentation - Mi Feng; Rui Zhou; Zhaolong Zhu; Yantian Xie; Minghan Zhu; Zhanyu Guo; Xinghui Feng; Dongxia Fu; Jianhua Chen; Yanhong Du; Yao Huang (Chemical Engineering Journal, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

A novel inactivated oral rabies vaccine with the incorporation of U-OMP19 enhances the immunogenicity by reducing viral proteins degradation and activating dendritic cells in a mouse model - Zonghui Zeng; Di Wu; Jingyi Xiong; Jianqing Zhao; Chuan Liang; Qiong Wu; Chengli Huang; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Z-Ligustilide restricts rabies virus replication by inducing ferroptosis through the ACSL4-LPCAT3-POR pathway - Jianqing Zhao; Qianruo Wang; Zhenkun Liu; Meixin Sun; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Estimating epidemic trajectories of SARS-CoV-2 and influenza A virus based on wastewater monitoring and a novel machine learning algorithm - Songzhe Fu; Yixiang Zhang; Yinghui Li; Ziqiang Zhang; Chen Du; Rui Wang; Yuejing Peng; Zhijiao Yue; Zheng Xu; Qinghua Hu (Science of The Total Environment, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Stubble height and irrigation significantly influenced the carbon footprint of ratoon rice cropping system in South China - Xiangyu Hu; Youqiang Fu; Nanxun Huang; Xinyu Wang; Rui Hu; Xuhua Zhong; Junfeng Pan; Meijuan Li; Yanzhuo Liu; Qunhuan Ye; Yuanhong Yin; Kaiming Liang (Field Crops Research, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

End-to-end stereo matching network with two-stage partition filtering for full-resolution depth estimation and precise localization of kiwifruit for robotic harvesting - Xudong Jing; Hanhui Jiang; Shiao Niu; Haosen Zhang; Bryan Gilbert Murengami; Zhenchao Wu; Rui Li; Chengquan Zhou; Hongbao Ye; Jinyong Chen; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

A hydro-mechanical closed form solution for the minimum safety thickness of water‑resistant rock in a karst tunnel under drag force in the connected fracture - Rui Qian; Qianqi Zhang; Qianfeng Xiao; Wenxi Fu; Guangchao Lv; Fei Ye (Tunnelling and Underground Space Technology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

“Fast-charging” mechanism of Li3VO4 from the perspective of material science for lithium-ion battery - Rui Wang; Yuan Li; Gaoyang Li; Yihan Fu; Youzhi Wu; Fen Ran (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

QTL mapping and omics analysis to identify genes controlling kernel dehydration in maize - Xining Jin; Xiaoxiang Zhang; Pingxi Wang; Juan Liu; Huaisheng Zhang; Xiangyuan Wu; Rui Song; Zhiyuan Fu; Shilin Chen (Theoretical and Applied Genetics, 2024)

A data-driven computational framework for non-intrusive reduced-order modelling of turbulent flows passing around bridge piers - Chuanhua Zhu; Dunhui Xiao; Jinlong Fu; Yuntian Feng; Rui Fu; Jinsheng Wang (Ocean Engineering, 2024)

Efficient and scalable prediction of stochastic reaction–diffusion processes using graph neural networks - Zhixing Cao; Rui Chen; Libin Xu; Xinyi Zhou; Xiaoming Fu; Weimin Zhong; Ramon Grima (Mathematical Biosciences, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

A Janus textile mimics leaf stoma for dynamic thermal regulation through a shape memory coating - Yuanxiang Xiao; Rui Cai; Shuangfei Xiang; Shujun Zhao; Feiya Fu; Hongyan Diao; Xiangdong Liu (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Management strategy evaluation operating model conditioning: a swordfish case study - Daniela Rosa; Iago Mosqueira; Dan Fu; Rui Coelho (Reviews in Fish Biology and Fisheries, 2024)
Evaluation of fish stock status is a key step for fisheries management. Tuna Regional Fisheries Management Organizations (t-RFMOs) are moving towards management strategy evaluation (MSE), a process that combines science and policy and depends on technical aspects, developed by scientists, designed to meet management objectives established by managers and other stakeholders. In the Indian Ocean, the current management advice for swordfish ( Xiphias gladius ) is based on an ensemble of 24 models considering four areas of uncertainty about the stock dynamics. There is an ongoing MSE process for swordfish, and this paper describes the methodology being applied for the conditioning of the operating model (OM), including model selection and validation. In the MSE, nine sources of uncertainty were considered, each being characterized by 2–3 levels. A partial factorial design was employed to reduce the number of models from a full factorial design to those needed to encompass the overall uncertainty. A selection and validation process was carried out, filtering models that converged, showed good predictive skills, and provided plausible estimates. Overall, the estimated spawning stock biomass (SSB) relative to SSB at maximum sustainable yield (MSY), and fishing mortality (F) relative to F MSY encompasses the estimates of the stock assessment ensemble at the most optimist area of the distribution. The MSE for swordfish is an ongoing process that is expected to provide more robust management advice in the future. Further developments to the OM can still occur, but the methods presented herein can be applied to this, or other species, MSE processes.

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

A new algorithm of critical control rod position search in MC code - Rui Li; Yuanguang Fu; Peng Liu; Dunfu Shi; Li Deng; Haibo Xu (Annals of Nuclear Energy, 2024)

Geogenic high arsenic elevates the groundwater antibiotic resistomes: A blind spot of resistance in Anthropocene - Rui Xu; Lingzhi Zhang; Fu-Yi Huang; Yong-Guan Zhu; Yi Zhao; Huaming Guo (Water Research, 2024)

Zircon U–Pb geochronology and geochemistry of Paleoproterozoic quartz monzonite in the Northern Yangtze Craton: Petrogenesis and geological implications - Wen-Xiang Zhang; Rui Li; Guang-Yan Zhou; Zhi-Fu Liu; Yuan-Bao Wu (Precambrian Research, 2024)

Dynamics changes in metabolites and pancreatic lipase inhibitory ability of instant dark tea during liquid-state fermentation by Aspergillus niger - Haoran Sun; Ranqin Fan; Rui Fang; Shanshan Shen; Yu Wang; Jialin Fu; Rui Hou; Runchen Sun; Shinuo Bao; Qi Chen; Pengxiang Yue; Xueling Gao (Food Chemistry, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Wastewater surveillance together with metaviromic data revealed the unusual resurgence of infectious diseases after the first wave of the COVID-19 outbreak - Ziqiang Zhang; Fenglan He; Liu Yi; Zhiqiang Deng; Rui Wang; Lixin Shen; Songzhe Fu (Journal of Hazardous Materials, 2024)

A novel micro-mechanical anisotropic elastic–plastic damage model for understanding time-dependent behaviors on rock-like materials - Qiaojuan Yu; Shigui Du; Qi-Zhi Zhu; Jian-Fu Shao; Rui Yong (International Journal of Rock Mechanics and Mining Sciences, 2024)

Activating the synergistic effect in Ni-Co bimetallic MOF for enhanced plasma-assisted ammonia synthesis - Yuhang Jing; Feng Gong; Sijun Wang; Wenbin Wang; Peng Yang; Enkang Fu; Rui Xiao (Fuel, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Toxic Metal Soil Speciation, Corn Accumulation and Health Risk Assessment in Acidic red soil Farmland in Mineral Industry Area - Yu Qian; Xiaoqi Li; Jie Yang; Rui Zhou; Zijin Hong; Change Liu; Shiyu Li; Yonggui Zhao; Denggao Fu; Ying Pan; Huan Feng; Marek Kolenčík; et al. (Water, Air, & Soil Pollution, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Effect of Licorice on Gene Expression Related to the Growth of Asian Seabass Lates calcarifer - Rui Yang; Wang Zhao; Yifu Wang; Zhengyi Fu; Jing Hu; Shengjie Zhou; Minghao Li; Zhenhua Ma (Journal of Marine Science and Engineering, 2024)
The Asian seabass (Lates calcarifer) has high economic value and is the primary aquaculture species in China. Licorice (Glycyrrhiza uralensis) as a feed additive has demonstrated significant immunological benefits in aquaculture. However, its effects on the growth of aquatic animals are largely unexplored. This study explored the influence of licorice on the level of growth-related genes in Asian seabass by conducting an experiment using artificial feed with 0%, 1%, 3%, and 5% licorice. The impact on growth performance and the expression of several genes, including growth hormone–releasing hormone (GHRH), growth hormone (GH), growth hormone receptor (GHR), insulin-like growth factor 1 (IGF1), IGF2, IGF2 receptor (IGF2R), myostatin 1 (MSTN1), and myostatin 2 (MSTN2), were studied over 56 d. According to the results, the 3% and 5% licorice-supplemented diets significantly improved survival rates and weight gain compared to the control group. Licorice affected the level of growth-associated genes in Asian seabass and significantly increased the levels of GHR and IGF1 in the liver. However, a 5% licorice diet downregulated the expression of IGF2. As the licorice content in the diet increased, the levels of IGF2R and MSTN1 in the muscle tissue first decreased and then increased, and licorice addition inhibited the MSTN2 expression. The inclusion of licorice in the feed led to a significant downregulation of the GH and GHRH expression (p

Antioxidant and Metabolic Response to Acute Acidification Stress of Juvenile Yellowfin Tuna (Thunnus albacares) - Xiaoyan Wang; Rui Yang; Zhengyi Fu; Lei Zhao; Zhenhua Ma (Journal of Marine Science and Engineering, 2024)
This study aimed to explore the impact of acute acidification on the antioxidant, metabolic performance, and liver histology of juvenile yellowfin tuna. The experiment subjected juvenile yellowfin tuna to a pH gradient environment of 8.1, 7.6, 7.1, and 6.6 for 48 h. The findings indicate that a seawater pH of 7.1 significantly impacts the antioxidant and metabolic systems of the juvenile yellowfin tuna in comparison to the control group. At pH 7.1, there were observed increases in glutathione reductase (GR), total antioxidant capacity (T-AOC), lactate dehydrogenase (LDH), hexokinase (HK), pyruvate kinase (PK), sodium-potassium ATPase (Na+K+-ATP), and calcium-magnesium ATPase (Ca2+Mg2+-ATP). Conversely, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TGs) were not significantly different across the treatment groups. However, an increase in transaminases at pH 7.1 suggested potential liver damage, which was further supported by observed structural liver tissue degeneration and hepatocyte vacuolation. In conclusion, under conditions of acute acidification stress, there is a decrease in antioxidant capacity and a suppression of metabolic levels in juvenile yellowfin tuna, leading to oxidative damage. This study lays the foundation for an in-depth understanding of the response mechanisms of juvenile yellowfin tuna in response to seawater acidification as well as healthy tuna farming in the broader context of seawater acidification.

Optimizing grape growth, berry quality and phenolic compounds with foliar co-application of iron and calcium - Yaqi Wang; Huiling Ma; Xiaoke Fu; Haoyu Wang; Rui Wang (South African Journal of Botany, 2024)

The boom era of emerging contaminants: A review of remediating agricultural soils by biochar - Renjie Hou; Jian Zhang; Qiang Fu; Tianxiao Li; Shijun Gao; Rui Wang; Shan Zhao; Bingyu Zhu (Science of The Total Environment, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

Preparation of Fe3O4 magnetic nanomaterials for the enrichment of phosvitin phosphopeptides - Shuze Ren; Songming Li; Mahmoud Abou-Elsoud; Rui Cui; Xing Fu; Xi Huang (Food Bioscience, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

A methodological review of compound-specific radiocarbon analysis for polycyclic aromatic hydrocarbons in environmental matrices - Yu Fu; Rui Zhang; Shaopeng Rong; Yuling Wu; Ying Wu; Miaolei Ya (Environmental Pollution, 2024)

A dimensionless capacity design method for combined cooling, heating, and power (CCHP) systems based on energy matching performance - Zhihao Fu; Lejun Feng; Jun Sui; Jiayu Chu; Rui Dong (Energy and Buildings, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Social determinants of health and their relation to suboptimal health status in the context of 3PM: a latent profile analysis - Lai Kun Tong; Yue Yi Li; Yong Bing Liu; Mu Rui Zheng; Guang Lei Fu; Mio Leng Au (EPMA Journal, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Morphological estimation of primary branch length of individual apple trees during the deciduous period in modern orchard based on PointNet++ - Xiaoming Sun; Leilei He; Hanhui Jiang; Rui Li; Wulan Mao; Dong Zhang; Yaqoob Majeed; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Hypoxia inducible factor-1α facilitates transmissible gastroenteritis virus replication by inhibiting type I and type III interferon production - Yunhang Zhang; Xue Rui; Yang Li; Yue Zhang; Yifei Cai; Chen Tan; Ning Yang; Yuanyuan Liu; Yuguang Fu; Guangliang Liu (Veterinary Microbiology, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Mechanistic insights into the stepwise lithium-mediated electrochemical nitrogen reduction for enhanced ammonia synthesis - Peng Yang; Feng Gong; Chaozhen Liu; Shenglin Liu; Enkang Fu; Yuhang Jing; Junjie Feng; Wenbo Tang; Rui Xiao (Chemical Engineering Journal, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Automated segmentation of individual leafy potato stems after canopy consolidation using YOLOv8x with spatial and spectral features for UAV-based dense crop identification - Hanhui Jiang; Bryan Gilbert Murengami; Liguo Jiang; Chi Chen; Ciaran Johnson; Fernando Auat Cheein; Spyros Fountas; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Detecting anomalous commuting patterns: Mismatch between urban land attractiveness and commuting activities - Zhaomin Tong; Ziyi Zhang; Rui An; Yaolin Liu; Huiting Chen; Jiwei Xu; Shihang Fu (Journal of Transport Geography, 2024)

Bioinspired breathable biodegradable bioelastomer-based flexible wearable electronics for high-sensitivity human-interactive sensing - Chenlin Huang; Mingyue Xiao; Zehui Li; Zihong Fu; Rui Shi (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Eco-driving strategy for connected electric buses at the signalized intersection with a station - Yali Zhang; Rui Fu; Yingshi Guo; Wei Yuan (Transportation Research Part D: Transport and Environment, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Analysis of vortex merging from a rotating tank laboratory experiment - Minghan Fu; Guoqing Han; Xiaojie Lu; Wenjin Sun; Joel Sommeria; Alexandre Stegner; Rui M.A. Caldeira; Changming Dong (Progress in Oceanography, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Chuaria Walcott from the early Cambrian Qingjiang biota: a taxon persisted for billions of years - Rui-Yun Li; Dong-Jing Fu; Xing-Liang Zhang (Palaeoworld, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

The Photoperiod Significantly Influences the Growth Rate, Digestive Efficiency, Immune Response, and Antioxidant Activities in the Juvenile Scalloped Spiny Lobster (Panulirus homarus) - Yinggang Wang; Rui Yang; Zhengyi Fu; Zhenhua Ma; Zemin Bai (Journal of Marine Science and Engineering, 2024)
This study aimed to elucidate the effects of different photoperiods (0 L:24 D, 6 L:18 D, 12 L:12 D, 18 L:6 D, 24 L:0 D, “Light (L) and Dark (D)”) on the growth performance and physiological responses of the juvenile scalloped spiny lobster (Panulirus homarus). Over a period of 56 days, parameters such as growth rate, digestive enzyme, immune enzyme, and antioxidant enzyme were meticulously evaluated in 90 lobsters subjected to these varying light conditions. The present study found no significant differences in survival rate (SR), molting frequency (MF), and meat yield production (MYP) among the various photoperiod treatments (p > 0.05). Notably, the highest weight gain rate (WGR) and specific growth rate (SGR) were observed under a 12 L:12 D photoperiod. In the continuous dark phase (0 L:24 D), pepsin (PEP) activity remained high in gastric tissues, while trypsin (TRYP) and chymotrypsin (CHT) activities reached the highest in hepatopancreas tissues. The α-amylase (AMS) activity in the hepatopancreas was most elevated under 18 L:6 D, and the optimal lipase (LPS) activity was recorded under 12 L:12 D. The activity of acid phosphatase (ACP) in the hepatopancreas was highest in the absence of light (0 L:24 D), whereas the activities of alkaline phosphatase (AKP) and lysozyme (LZM) were most effective under the 12 L:12 D photoperiod. The total antioxidant capacity (T-AOC), along with catalase (CAT) and superoxide dismutase (SOD) activities of the hepatopancreas reached the highest at 12 L:12 D. The highest activity of glutathione peroxidase (GSH-Px) was seen under 18 L:6 D. The concentration of malondialdehyde (MDA), a marker of oxidative stress, was found to be highest under 12 L:12 D. Consequently, this specific photoperiod is essential for achieving optimal growth and maintaining appropriate physiological balance in the scalloped spiny lobster during aquaculture. These findings provide a foundational guideline for establishing the lighting environment in the farming of the juvenile scalloped spiny lobster.

Vertical variation of source-apportioned PM2.5 and selected volatile organic compounds near an elevated expressway in an urban area - Ho-Tang Liao; Chien-Mei Yen; Yu-Rui Chen; Jyun-De Wu; Shih-Wei Tsai; Chang-Fu Wu (Environmental Science and Pollution Research, 2024)

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Improved binocular localization of kiwifruit in orchard based on fruit and calyx detection using YOLOv5x for robotic picking - Changqing Gao; Hanhui Jiang; Xiaojuan Liu; Haihong Li; Zhenchao Wu; Xiaoming Sun; Leilei He; Wulan Mao; Yaqoob Majeed; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Monitoring and prediction of Aeromonas veronii dynamics via absolute quantification microbiome sequencing facilitated the development of a risk assessment tool in a shrimp farm - Wenyu Zhao; Rui Wang; Yixiang Zhang; Qian Zhang; Songzhe Fu (Aquaculture, 2024)

Regional background ozone estimation for China through data fusion of observation and simulation - Zhixu Sun; Jiani Tan; Fangting Wang; Rui Li; Xinxin Zhang; Jiaqiang Liao; Yangjun Wang; Ling Huang; Kun Zhang; Joshua S. Fu; Li Li (Science of The Total Environment, 2024)

Targeted amplicon sequencing facilitated a novel risk assessment framework for assessing the prevalence of broad spectrum bacterial and coronavirus diseases - Songzhe Fu; Haifeng Li; Fenglan He; Rui Wang; Yixiang Zhang; Ziqiang Zhang; Hui Li (Science of The Total Environment, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

Reducing infertile eggs and dead embryos during egg hatching based on respiration - Jiaojiao Wang; Rui Cao; Qiaohua Wang; Meihu Ma; Dandan Fu (Journal of Cleaner Production, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Dynamic Effect of Landslides Triggered by Earthquake: A Case Study in Moxi Town of Luding County, China - Hongfu Zhou; Fei Ye; Wenxi Fu; Bin Liu; Tian Fang; Rui Li (Journal of Earth Science, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

RETRACTED: Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2024)

Construction of hypoallergenic microgel by soy major allergen β-conglycinin through enzymatic hydrolysis and lactic acid bacteria fermentation - Yumeng Fu; Xinran Guo; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

Enhanced and selective uranium extraction onto electrospun nanofibers by regulating the functional groups and photothermal conversion performance - Dingyang Chen; Xinyue Zhao; Minsi Shi; Xingyu Fu; Wei Hu; Xiaoyuan Shi; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2024)

Shifted plant composition predominantly controls nitrogen addition effect on community-level leaf nutrient resorption in a boreal peatland - Rui Li; Pan-Pan Wu; Chao Peng; Fu-Xi Shi; Rong Mao (Plant and Soil, 2024)

The data as a production factor: nonlinear effects of factor efficiency on haze pollution - Mei-Rui Zhong; Jia-Yu Fu; Han Zou (Environment, Development and Sustainability, 2023)

Longitudinal wastewater surveillance of four key pathogens during an unprecedented large-scale COVID-19 outbreak in China facilitated a novel strategy for addressing public health priorities–A proof of concept study - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiqiang Deng; Fenglan He; Xiaotong Jiang; Lixin Shen (Water Research, 2023)

Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

The roles of Methylobacterium organophilum and Sphingomonas melonis for accelerating N-methyl pyrrolidone (NMP) biodegradation - Yongyi Gao; Ting Chen; Yifan Hou; Ruiyun Xue; Rui Liu; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Water Process Engineering, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Assessments of Tensile Characteristics and Degradation Mechanism of Sandstone Subjected to Wetting–Drying Cyclic Treatment - Rui Li; Changtai Zhou; Yizi Fu; Jianbo Zhu (Rock Mechanics and Rock Engineering, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Light grazing reduces gaseous nitrogen emissions from temperate grassland soils during freeze‒thaw cycles: An intact core incubation study - Chenjun Du; Xing Wu; Fangfang Wang; Rui Wang; Xunhua Zheng; Yihe Lü; Bojie Fu (Soil Biology and Biochemistry, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

4-Phenylbutyric acid may prevent mouse ovarian and uterine damage due to procymidone-induced alteration of circRNA Scar and circZc3h4 levels by controlling excessive unfolded protein response - Rui Li; Fan Li; Xuning Wang; Mingxin Bai; Hu Fu; Zhengli Yan; Xiaoping Yang; Yongfei Zhu (Pesticide Biochemistry and Physiology, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

A novel culture-enriched metagenomic sequencing strategy effectively guarantee the microbial safety of drinking water by uncovering the low abundance pathogens - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiguang Qiu; Weizhi Song; Qian Yang; Lixin Shen (Journal of Environmental Management, 2023)

Modulation of soy protein immunoreactivity by different matrix structures of lactic acid bacterium-induced soy protein gels: Epitope destruction during in vitro gastroduodenal digestion and absorption - Yaqiong Wang; Yumeng Fu; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

Fruit detachment force of multiple varieties kiwifruit with different fruit-stem angles for designing universal robotic picking end-effector - Wentai Fang; Zhenchao Wu; Weiwu Li; Xiaoming Sun; Wulan Mao; Rui Li; Yaqoob Majeed; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Twice matched fruit counting system: An automatic fruit counting pipeline in modern apple orchard using mutual and secondary matches - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Fangfang Gao; Rui Li; Longsheng Fu; Dong Zhang; Spyros Fountas (Biosystems Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Highly stable and selective Pt/TS-1 catalysts for the efficient nonoxidative dehydrogenation of propane - Weilong Hou; Kehang Lin; Xiangyu Zhang; Bowen Xu; Yuexia Wang; Xinqing Lu; Yijing Gao; Rui Ma; Yanghe Fu; Weidong Zhu (Chemical Engineering Journal, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Mechanism analysis and improved molecular modification: Design of high efficiency and environmentally friendly triazole fungicide substitutes - Jiaxuan Gao; Xinao Li; Rui Fu; Yu Li (Chemosphere, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Reducing carbon footprints and increasing net ecosystem economic benefits through dense planting with less nitrogen in double-cropping rice systems - Wentao Zhou; Wenfei Long; Hongrui Wang; Pan Long; Ying Xu; Kangyu Zhong; Rui Xiong; Feipeng Xie; Fugui Chen; Zhiqiang Fu (Science of The Total Environment, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Energy-oriented control retrofit for existing HVAC system adopting data-driven MPC – Methodology, implementation and field test - Bao Yue; Bing Su; Fu Xiao; Anbang Li; Kehua Li; Shen Li; Rui Yan; Qiuzhuang Lian; Ao Li; Yuanyang Li; Xing Fang; Xingang Liang (Energy and Buildings, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

A new oleanane-type triterpene from Ardisia lindleyana D.Dietr and its cytotoxic activity - Zhou Tiqiang; Wei Zhenzhen; Fu Qianyu; Qiu Rui; Zhang Guangjie; Li Bin; Dong Junxing; Zeng Chengchu (Natural Product Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

NDMFCS: An automatic fruit counting system in modern apple orchard using abatement of abnormal fruit detection - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Wulan Mao; Rui Li; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Satellite observed response of fire dynamics to vegetation water content and weather conditions in Southeast Asia - Yuyun Fu; Jiheng Hu; Weiguo Song; Yuanxi Cheng; Rui Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Screening eco-friendliness tire antioxidants alternatives: functional 2,2,4-trimethyl-1,2-dihydroquinoline derivatives design and toxicity evaluation - Yu Wang; Rui Fu; Peixuan Sun; Xinao Li; Wenjin Zhao (Environmental Science and Pollution Research, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Innovative screening for functional improved aromatic amine derivatives: Toxicokinetics, free radical oxidation pathway and carcinogenic adverse outcome pathway - Yajing Liu; Xinao Li; Qikun Pu; Rui Fu; Zhonghe Wang; Yu Li; Xixi Li (Journal of Hazardous Materials, 2023)

Experimental and numerical study on the ignition delay times of methane/propane mixtures diluted in carbon dioxide - Wenxiang Xia; Chun Zou; Yi Yuan; Rui Fu; Jiacheng Liu; Chao Peng (Fuel, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

Potential thyroid hormone disorder risks of tire antioxidants to aquatic food chain organisms after absorbing free radicals in marine and freshwater environments - Yu Wang; Rui Fu; Xinao Li; Wenjin Zhao; Miao Liu; Yu Li (Aquatic Toxicology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Effects of Enterobacter sp. Zm-123 and spent mushroom substrate on rape growth promotion and cadmium toxicity reduction in cadmium-contaminated soil - Yu Jin; Rui Yang; Yongduo Guan; Xiaochen Liu; JiaHui Fu; Xuesheng Liu; Juanjuan Qu (Journal of Soils and Sediments, 2023)

Changes in the factors controlling Northeast Asian spring surface air temperature in the past 60 years - Shanshan Fu; Zhiwei Zhu; Rui Lu (Climate Dynamics, 2023)

Thin wire segmentation and reconstruction based on a novel image overlap-partitioning and stitching algorithm in apple fruiting wall architecture for robotic picking - Hanhui Jiang; Xiaoming Sun; Wentai Fang; Longsheng Fu; Rui Li; Fernando Auat Cheein; Yaqoob Majeed (Computers and Electronics in Agriculture, 2023)

Phenotyping of individual apple tree in modern orchard with novel smartphone-based heterogeneous binocular vision and YOLOv5s - Guanao Zhao; Ruizhe Yang; Xudong Jing; Haosen Zhang; Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Rui Li; Xiaofeng Wei; Spyros Fountas; Huijun Zhang; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Genome-Wide Identification and Expression Analysis of the CAD Gene Family in Walnut (Juglans regia L.) - Pengyu Wu; Rui Zhang; Shangqi Yu; Jiazhi Fu; Zhongzhong Guo; Dong Li; Zhiyong Pan; Haifang Hu (Biochemical Genetics, 2023)

Speed and temperature superposition on traffic speed deflectometer measurements - Miaomiao Zhang; Guozhi Fu; Yuetan Ma; Rui Xiao; Baoshan Huang (Transportation Geotechnics, 2023)

Growth, nutrient uptake and transcriptome profiling of rice seedlings in response to mixed provision of ammonium- and nitrate-nitrogen - Youqiang Fu; Xuhua Zhong; Chusheng Lu; Kaiming Liang; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Qunhuan Ye; Yanzhuo Liu (Journal of Plant Physiology, 2023)

Mechanistic studies of polyphenols reducing the trypsin inhibitory activity of ovomucoid: Structure, conformation, and interactions - Rui Cui; Shengnan Ji; Minquan Xia; Xing Fu; Xi Huang (Food Chemistry, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Green finance network evolution and prediction: fresh evidence from China - Rui Ding; Yiming Du; Linyu Du; Jun Fu; Shihui Chen; Kexin Wang; Wenqian Xiao; Lina Peng; Juan Liang (Environmental Science and Pollution Research, 2023)

Identifying the water quality variation characteristics and their main driving factors from 2008 to 2020 in the Yellow River Basin, China - Shasha Liu; Yue Qiu; Rui Fu; Yun Liu; Chengyu Suo (Environmental Science and Pollution Research, 2023)

A novel pollination robot for kiwifruit flower based on preferential flowers selection and precisely target - Changqing Gao; Leilei He; Wentai Fang; Zhenchao Wu; Hanhui Jiang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

Repetitive transcranial magnetic stimulation enhances the neuronal excitability of mice by regulating dynamic characteristics of Granule cells’ Ion channels - Haijun Zhu; Xiaonan Yin; Huilan Yang; Rui Fu; Wentao Hou; Chong Ding; Guizhi Xu (Cognitive Neurodynamics, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to “Limited hydrolysis of glycosylated whey protein isolate ameliorates the oxidative and physical stabilities of conjugated linoleic acid oil-in-water emulsions” [Food Chem. 362 (2021)130212] - Meng Li; Rui Yu; Runxiao Fu; Yanting He; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

An interfacial gas-enrichment strategy for mitigating hydrate adhesion and blockage - Rui Ma; Senbo Xiao; Yuanhao Chang; Yuequn Fu; Jianying He; Zhiliang Zhang (Chemical Engineering Journal, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

Development of quantitative wastewater surveillance models facilitated the precise epidemic management of COVID-19 - Songzhe Fu; Fenglan He; Rui Wang; Wentao Song; Qingyao Wang; Wen Xia; Zhiguang Qiu (Science of The Total Environment, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Selection and modification of ground motion records using Newmark-Hall spectrum as target spectrum for long-period structures - Jianyu Fu; Dongsheng Wang; Rui Zhang; Xiaoyu Chen (Earthquake Engineering and Engineering Vibration, 2023)

The mechanism underlying the response of Agarophyton vermiculophyllum to desiccation–rehydration stress - Feng Fu; Rui Wang; Mingjie Zhao; Zehao Wu; Weiming Sun (Aquatic Botany, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Alternation of the Atmospheric Teleconnections Associated with the Northeast China Spring Rainfall during a Recent 60-Year Period - Zhiwei Zhu; Rui Lu; Shanshan Fu; Hua Chen (Advances in Atmospheric Sciences, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

The structure and subduction relicts of the Changchun–Yanji suture, NE China: new evidence from deep seismic reflection profiling - Jiaduo Zhang; Hesheng Hou; Jianbo Zhou; Wei Fu; Rui Guo; Zongdong Pan; Hengcheng Ying (International Journal of Earth Sciences, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Evaluation of Port–Hinterland Synergy Level Considering Fixed Asset Allocation and Social Commodity Circulation under the “Dual Circulation” Development Pattern - Zhaohui Li; Yujin Huang; Fan Yang; Yi Li; Yan Fang; Rui Fu (Journal of Marine Science and Engineering, 2022)
“Port–hinterland synergy” means the development of port and hinterland should promote each other. The “dual circulation” development pattern indicates the requirement of exploring the domestic transportation demand and promoting the integration between ports and hinterlands. However, the current research on the synergy level between ports and hinterlands is not enough to meet the needs of constructing a “dual circulation” development pattern, and few studies have explored the influencing factors of port–hinterland synergy level directly, especially in the context of the new development pattern of “dual circulation”. After investigating the synergetic mechanism between ports and hinterlands, this study proposes to further consider the influence of fixed assets allocation and social commodity circulation on the synergy level under the “dual circulation” pattern. So, fixed asset investment and three different forms of commodity circulation activities are selected to represent the corresponding hinterland’s economic activities and added into the evaluation indices. To assess ports’ responsiveness to different kinds of transport demand, throughputs of each port are divided into those of domestic and foreign countries. Then this paper evaluates the level of port–hinterland synergy by the coupling synergy model, and the influence degree of these activities on the synergy level was studied with the partial least squares regression (PLS). The results show that there is heterogeneity in regional and port positioning in the port–hinterland synergy level, and that four selected economic activities’ improvement can enhance the port–hinterland synergy level. Among them, retail industry has the strongest positive effect, followed by tertiary industry, import and export trade, and fixed asset investment.

Spatiotemporal variations of water quality and their driving forces in the Yangtze River Basin, China, from 2008 to 2020 based on multi-statistical analyses - Shasha Liu; Rui Fu; Yun Liu; Chengyu Suo (Environmental Science and Pollution Research, 2022)

Recombinant AcMNPV-gp64-EGFP and synergist triphenyl phosphate, an effective combination against Spodoptera frugiperda - Rui Jiao; Yuejun Fu (Biotechnology Letters, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Characteristics of summer cloud precipitation along latitude 30°N in East Asia derived from Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner measurements - Mengxiao Wang; Yunfei Fu; Chun Zhao; Lei Zhong; Rui Li; Dongyong Wang; Xuexing Qiu; Shengnan Zhou (International Journal of Climatology, 2022)
There has been little systematic analysis of the influence of the three‐step staircase topography on the characteristics of precipitation along latitude 30°N in East Asia. After the distribution of atmospheric climate states over East Asia was analysed, in this study, the climatological characteristics of summer convective and stratiform precipitation on horizontal distribution, vertical structure, and diurnal variation in East Asia were investigated by using a merged dataset derived from the measurements of the Tropical Rainfall Measuring Mission Precipitation Radar and Visible and Infrared Scanner from 1998 to 2012 reanalysis datasets. Results indicate that the rain frequency, the mean rain rate, and the maximum echo reflectivity factor show clear differences among the three‐step staircase topography, especially between the first staircase and its eastern region. There are small changes in the echo‐top height, the cloud‐top height, the maximum echo reflectivity factor and its corresponding height from the East China Sea westwards to the eastern part of the first staircase, passing the third staircase and the second staircase along 30°N. However, the rain rate decreased obviously twice westwards along this latitude, which responds to aerosol indirect effect and humidity effect, respectively. The diurnal variation of the convective precipitation reflectivity factor indicated that the development of convection in the eastern part of the first staircase gets at the maximum from the early afternoon to sunset, whereas the strongest echo reflectivity factor of precipitation in the second and third staircases including the East China Sea appears in the early morning, which is consistent with the diurnal variations of the atmospheric circulation.

Effects of the soaking-related parameters in a combined freezing-based seawater desalination process - Hui Yang; Yuanfei Jiang; Rui Wang; Bingyan Dong; Mengxiao Fu (Environmental Science and Pollution Research, 2022)

Impacts of Topographic Complexity on Modeling Moisture Transport and Precipitation over the Tibetan Plateau in Summer - Gudongze Li; Haoming Chen; Mingyue Xu; Chun Zhao; Lei Zhong; Rui Li; Yunfei Fu; Yanhong Gao (Advances in Atmospheric Sciences, 2022)
The non-hydrostatic global variable resolution model (MPAS-atmosphere) is used to conduct the simulations for the South Asian Summer monsoon season (June, July, and August) in 2015 with a refinement over the Tibetan Plateau (TP) at the convection-permitting scale (4 km). Two experiments with different topographical datasets, complex (4-km) and smooth (60-km) topography, are designed to investigate the impacts of topographical complexity on moisture transport and precipitation. Compared with the observations and reanalysis data, the simulation can successfully capture the general features of key meteorological fields over the TP despite slightly underestimating the inflow through the southern TP. The results indicate that the complex topography can decrease the inward and outward moisture transport, ultimately increasing the total net moisture transport into the TP by ∼11%. The impacts of complex topography on precipitation are negligible over the TP, but the spatial distributions of precipitation over the Himalayas are significantly modulated. With the inclusion of complex topography, the sharper southern slopes of the Himalayas shift the lifted airflow and hence precipitation northward compared to the smooth topography. In addition, more small-scale valleys are resolved by the inclusion of complex topography, which serve as channels for moisture transport across the Himalayas, further favoring a northward shift of precipitation. Overall, the difference between the two experiments with different topography datasets is mainly attributed to their differing representation of the degree of the southern slopes of the Himalayas and the extent to which the valleys are resolved.

Impact of N application rate on tea (Camellia sinensis) growth and soil bacterial and fungi communities - Sheng Tang; Jingjie Zhou; Wankun Pan; Rui Tang; Qingxu Ma; Meng Xu; Tong Qi; Zhengbo Ma; Haoran Fu; Lianghuan Wu (Plant and Soil, 2022)

Sucrose Induced HMGR to Promote Ginsenoside Biosynthesis in the Growth of Wild Cultivated Ginseng (Panax ginseng) - Rui Ma; Baoyu Fu; Pengdi Yang; Xiaoyu Teng; Daqing Zhao; Rui Jiang; Liwei Sun (Journal of Soil Science and Plant Nutrition, 2022)

Synergistic Effect and Mechanism of Apoptosis Induction by Morphine and the HIV-1gp120V3 Loop in Hippocampal Neurons - Xueqin Yan; Zheng Gong; Rui Pan; Huili Wang; Haijie Tang; Hanyang He; Saixian Wen; Yongmei Fu; Jun Dong (Journal of Neuroimmune Pharmacology, 2022)

Toxicities of nanomaterials and metals to rice under low atmospheric pressure - Kerui Guo; Dongheng Fu; Muhammed Adeel; Yunze Shen; Kexiang Wang; Yi Hao; Tonghao Bai; Yaoyao Wang; Yukui Rui (Acta Physiologiae Plantarum, 2022)

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

Distribution Analysis of Local Ice Pressures in the Indentation Test at Various Velocities - Guojun Wang; Qianjin Yue; Dayong Zhang; Yanghua Fu; Xin Peng; Rui Dong (Journal of Marine Science and Engineering, 2022)
When sea ice acts on vertical structures, there are much higher pressures in localized areas known as high-pressure zones (HPZs) than in other areas. The damage failure mode of sea ice varies with the sea ice velocity and affects the distribution of HPZs. In this study, an indentation test that drives ice sheet interaction with a vertical rigid plate (indentor) was designed, and a pressure sensor (consisting of 32 × 32 small pressure units of 100 mm2) was installed on the indentor face to measure the local ice pressure (LIP) at various velocities. The distribution of the LIPs along the ice thickness, the probability distribution of the LIPs and the distribution relationship of the LIPS in space and time were obtained from the measurement. The results show that the LIPs were mainly distributed in the middle of the sea ice, which is consistent with full-scale observations and previous research. Ductile failure of the sea ice results in a larger LIP distribution area than brittle failure at the same threshold kt (kt = σL/σcr). The probability distribution of the LIPs decreases exponentially with increasing pressure and follows a lognormal distribution. The maximum LIP appears at the peak moment of the global force when the sea ice failure mode is mainly ductile failure. However, the maximum LIP may not occur at the peak moment when the sea ice failure is mainly brittle failure and, instead can appear at any moment in the global force time history curve. The HPZ (which is larger than 7/8 times the maximum LIP) area is less than 2% of the nominal contact area at various velocities. The influence of the sea ice velocity on the spatial and temporal distribution of LIP is analyzed, and the results provide a reference for designing structures with local strength in ice regions.

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Toward Exploring Topographic Effects on Evolution and Propagation of Ocean Mesoscale Eddies Through Life Cycle Across Izu-Ogasawara Ridge in Northwestern Pacific Ocean - Rui Nian; Xue Geng; Zhengguang Zhang; Minghan Yuan; Zhen Fu; Hengfu Xu; Hua Yang; Qi Lai; Hui He; Chi Wei Su; Lina Zang; Qiang Yuan; et al. (Frontiers in Marine Science, 2022)
Ocean mesoscale eddies contribute significantly to water transport on a global scale, constituting the ubiquitous, irregular, discrete, nonlinear components. In this manuscript, we propose to explore whether and how the topographic effect of one meridional ridge, could exert considerable influences on the evolution and propagation of mesoscale eddies through their life cycle, directly from the perspectives of real observation statistics. We systematically investigate the known variability of mesoscale eddy trajectories, derived by multimission satellite altimetry from 1993 to 2018, of a life cycle more than 6 months, over the Izu-Ogasawara Ridge, and quantitatively examined the eddy-ridge interaction by observation statistics and wavelet coherence map, with respect to the intrinsic attributes, namely, the amplitude, the rotation speed, the radius. Due to the spatial-temporal diversity, a series of correlative steps have been particularly designed along time-frequency domain to trace back mesoscale eddy trajectories in a variety of origins, location, lifespan, polarity, either completely or partially passing over the ridge, and to facilitate the standardization in statistics across three phases of their life cycle, i.e., before, during and after the interaction with the ridge. It has been revealed in our experiment that three intrinsic attributes of mesoscale eddies within 25 years, all demonstrated noticeable correlation with the variation of topographic relief over the ridge. We observed that most of the cyclonic eddies obviously tended to begin to decay or even demise, while on the contrary, some of the anticyclonic eddies preferred to intensify slightly, or making no significant difference when encountering the upslope until climbing across the top, basically consistent with the expectation of potential vorticity (PV) conservation. The drifting velocity agreed with the tendency that the direction would be more probably modified toward equatorward or poleward by forcing to meridional component, with zonal component reduced at the beginning. The mesoscale eddies with the passage over the ridge exhibited the relatively high average horizontal scales, amplitude, rotation speed on the whole, compared to those with only partially passage. The developed scheme could integrate more evidences on how mesoscale eddies response to the topographic effects during their time-varying evolution and propagation process, and help provide opportunities to potentially identify and predict the underlying dynamic patterns and mechanisms that mesoscale eddies engage in ocean dynamics when proceeding toward meridional ridges on a global scale, with the promise of the end-to-end data-driven solution, such as deep learning architecture involved in the future.

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

Cognition effectiveness of continuous positive airway pressure treatment in obstructive sleep apnea syndrome patients with cognitive impairment: a meta-analysis - Xinzhao Jiang; Zicong Wang; Nan Hu; Ying Yang; Rui Xiong; Zhengqi Fu (Experimental Brain Research, 2021)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

miR-106b-5p upregulation is associated with microglial activation and inflammation in the mouse hippocampus following status epilepticus - Tao Yu; Hui Fu; Jing-Jing Sun; Dan-Rui Ding; Hua Wang (Experimental Brain Research, 2021)

Cyclic response of monopile-supported offshore wind turbines under wind and wave loading in sand - Rui Liang; Yu Yuan; Dengfeng Fu; Run Liu (Marine Georesources & Geotechnology, 2021)

Qingbo, a common cyprinid fish, responds diversely in behavior and locomotion to predators with different hunting modes - Cheng Fu; Lian-Chun Yi; Wen-Pei Wu; Chun-Xiao Sun; Rui-Na Liu; Shi-Jian Fu (Fish Physiology and Biochemistry, 2021)

A high-resolution timescale for the Miocene Shanwang diatomaceous shale lagerstätte (China): development of Wavelet Scale Series Analysis for cyclostratigraphy - Jifeng Yu; Xinlong Pang; Wenzhao Fu; Jason Hilton; Mingmei Liang; Zongkai Jiang; Xiuli Zhao; Wenyan Qiao; Suo Shi; Diandong Zhang; Huitao Cao; Haibo Jia; et al. (Geosciences Journal, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Ginsenoside Biosynthesis in Panax Ginseng with Red-Skin Disease Is Inhibited by Soil Characteristics - Rui Ma; Baoyu Fu; Shikuan Song; Chunyang Zhang; Xiajun Yuan; Tingshi Zhang; Daqing Zhao; Liwei Sun (Journal of Soil Science and Plant Nutrition, 2021)

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

The geochemical behavior of trace metals and nutrients in submerged sediments of the Three Gorges Reservoir and a critical review on risk assessment methods - Bin Wang; Shu Chen; Yuwei Chen; Nelson Belzile; Rui Zheng; Yuankun Yang; Kaibin Fu; Yongcan Chen; Binliang Lin; Zhaowei Liu; Jian Sun (Environmental Science and Pollution Research, 2021)

Temperature Significantly Regulates Gene Expressions of Vertebrae Chondrocytes and Osteoblasts in Juvenile Golden Pompano (Trachinotus ovatus) - Mingyang Han; Zhengyi Fu; Rui Yang; Jian G. Qin; Zhenhua Ma (Frontiers in Marine Science, 2021)
To elucidate the possible molecular reaction of vertebral fusion in juvenile golden pompano at high temperature, we examined the changes in growth, vertebral fusion incidence, histological differences and transcription levels of genes related to bone development in juvenile golden pompano at 27 and 33°C for 30 days, respectively. The growth rate of juvenile fish was faster when the water temperature was 33°C, but the incidence of vertebral fusion was higher. Prolonged high water temperature reduced the osteogenic layer in the growth zone of the vertebral endplate and the elastic externa. The endplate growth areas of the fused vertebrae were transformed into cartilage tissue, which was then remodeled into bone. The intervertebral notochord tissue was transformed into bone and the intervertebral space disappeared. In normal phenotypes of vertebrae, short-term high temperature could promote the expression of genes related to cartilage differentiation and maturation, as well as genes related to osteoblastic differentiation. With the increase of culture time, the expression of genes related to cartilage and osteogenesis development was inhibited. In fused vertebrae, cartilage proliferation was enhanced, osteogenic differentiation was inhibited, and matrix mineralization may be enhanced. Genes associated with the development of chondrocytes and osteoblasts in the vertebrae of juvenile Trachinotus ovatus were significantly regulated by temperature and time. The results may contribute to further understanding of the occurrence of vertebral fusion at high temperature.

Fast and accurate detection of kiwifruit in orchard using improved YOLOv3-tiny model - Longsheng Fu; Yali Feng; Jingzhu Wu; Zhihao Liu; Fangfang Gao; Yaqoob Majeed; Ahmad Al-Mallahi; Qin Zhang; Rui Li; Yongjie Cui (Precision Agriculture, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

High-resolution estimation of ambient sulfate concentration over Taiwan Island using a novel ensemble machine-learning model - Lulu Cui; Qingwei Ma; Rui Li; Hongbo Fu; Ziyu Zhang; Liwu Zhang; Ying Chen (Environmental Science and Pollution Research, 2021)

Influence of Non-protein Diets on Hepatic Metabolism and Endocrine in Barramundi (Lates calcarifer) - Zhengyi Fu; Shengjie Zhou; Gang Yu; Rui Yang; Mingyang Han; Zhenhua Ma (Frontiers in Marine Science, 2021)
This study evaluated the effects of different dietary non-protein energy sources on hepatic metabolism and endocrine of barramundi. Fish were fed iso-energy diets (18 MJ kg –1 ) with two types of non-protein energy source in the experimental group and a regular diet was used as the control. The feeding trial lasted 56 days. In the present study, CPT1 and SCD expression in fish fed high lipid diet were upregulated and liver lipid metabolism was more active than the control group. Serum biochemical parameters including serum glucose, serum triacylglycerol and serum cholesterol were significantly increased. The IGF-I and IGF-II expressions were significantly upregulated, and growth performances were improved in fish fed the high lipid diet. When barramundi were fed with the high carbohydrate diet, GK expression was downregulated and cPEPCK expression was upregulated, indicating that glycogen might accumulate in liver. The fluctuation of serum biochemical parameters and the growth performance were not significantly different compared to the control group. In conclusion, high lipid diet can shorten the raising period, but it causes the change of metabolic level and the increase of useless adipose tissue; The high carbohydrate diet did not significantly improve the growth performance, and no significant metabolic abnormalities were observed, indicating that carbohydrate has the potential to be the feed energy supply source for juvenile barramundi. The results provide insights for further understanding the availability of non-protein energy sources in the diet of juvenile barramundi.

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Effects of Rotifers Enriched With Different Enhancement Products on Larval Performance and Jaw Deformity of Golden Pompano Larvae Trachinotus ovatus (Linnaeus, 1758) - Zhengyi Fu; Rui Yang; Shengjie Zhou; Zhenhua Ma; Tao Zhang (Frontiers in Marine Science, 2021)
This study evaluated the effects of rotifers enriched with three enhancement products ( Nannochloropsis , S.presso, and Algamac 3080) on the body fatty acid composition, growth, survival, jaw deformity, and bone development-related gene expression of the golden pompano larvae. The rotifers enriched with Nannochloropsis were rich in EPA, and the rotifers enriched with S.presso and Algamac 3080 were rich in docosahexaenoic acid (DHA). The level of DHA in Algamac 3080 is higher than that in S.presso. The first feeding started at 3 DPH, and data were collected at 8 DPH. The results showed that the body fatty acid composition of the larvae was basically the same as that of the feeding rotifers. The specific growth rate of S.presso and Algamac 3080 treatment was significantly higher than the un-enriched treatment ( P < 0.05). The survival rate of Algamac 3080 treatment was significantly lower than the other treatments ( P < 0.05), and the jaw deformity rate of S.presso treatment was significantly lower than the Nannochloropsis and un-enriched treatment ( P < 0.05). The expression level of BMP2 and BMP4 in golden pompano larvae were not significantly affected by the enhancement products ( P > 0.05), and the expression level of RXRα decreased significantly in the S.presso and Algamac 3080 treatment ( P < 0.05). This study indicates that S.presso was an enhancement product more suitable for rotifers for golden pompano larvae. This study provided reliable reference and guidance for the first feeding of golden pompano larvae and also provided more reference data for the study of the mechanism of diet on larval fish bone deformity.

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)

Fundamental Characteristics of Tropical Rain Cell Structures as Measured by TRMM PR - Yunfei Fu; Yilun Chen; Xiangdong Zhang; Yu Wang; Rui Li; Qi Liu; Lei Zhong; Qiong Zhang; Aoqi Zhang (Journal of Meteorological Research, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

A semi-greedy neural network CAE-HL-CNN for SAR target recognition with limited training data - Rui Qin; Xiongjun Fu; Jian Dong; Wen Jiang (International Journal of Remote Sensing, 2020)

Transgenic merA and merB expression reduces mercury contamination in vegetables and grains grown in mercury-contaminated soil - Rui Li; Han Wu; Jing Ding; Nan Li; Weimin Fu; Lijun Gan; Yi Li (Plant Cell Reports, 2020)

Development of SNP markers for the bighead carp (Hypophthalmichthys nobilis) by using transcriptomic sequences - Rui An; Jianjun Fu; Bingjie Jiang; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Conservation Genetics Resources, 2020)

Fluoride-Induced Alteration in the Diversity and Composition of Bacterial Microbiota in Mice Colon - Rong Fu; Ruiyan Niu; Rui Li; Baijuan Yue; Xuhua Zhang; Qiqi Cao; Jundong Wang; Zilong Sun (Biological Trace Element Research, 2020)

Dynamic behaviour and damage characteristics of loess in Xianyang, China - Huie Chen; Hui Li; Rui Fu; Xiaoqing Yuan (Bulletin of Engineering Geology and the Environment, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Two-Dimensional Discrepancies in Fracture Geometric Factors and Connectivity Between Field-Collected and Stochastically Modeled DFNs: A Case Study of Sluice Foundation Rock Mass in Datengxia, China - Wen Zhang; Rui Fu; Chun Tan; Zhifa Ma; Ying Zhang; Shengyuan Song; Peihua Xu; Shuonan Wang; Yunpeng Zhao (Rock Mechanics and Rock Engineering, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Application of Rice Grain Husk Derived Biochar in Ameliorating Toxicity Impacts of Cu and Zn on Growth, Physiology and Enzymatic Functioning of Wheat Seedlings - Rui Wang; Weizhang Fu; Jinhua Wang; Lusheng Zhu; Lei Wang; Jun Wang; Zulfiqar Ahmad (Bulletin of Environmental Contamination and Toxicology, 2019)

Relationship between Extreme Precipitation and Temperature in Two Different Regions: The Tibetan Plateau and Middle-East China - Rui Wang; Tao Xian; Mengxiao Wang; Fengjiao Chen; Yuanjian Yang; Xiangdong Zhang; Rui Li; Lei Zhong; Chun Zhao; Yunfei Fu (Journal of Meteorological Research, 2019)

Metabolomics reveals the drought-tolerance mechanism in wild soybean (Glycine soja) - Xiaoxia Wang; Rui Guo; Mingxia Li; Yuan Liu; Mingli Zhao; Hui Fu; Xueying Liu; Shiyao Wang; Lianxuan Shi (Acta Physiologiae Plantarum, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Effects of periodical drying and non-drying on nutrient content and desiccation tolerance of an intertidal Pyropia yezoensis strain subject to farming conditions - Wen Jun Wang; Xiao Lei Li; Teng Qing Sun; Zhou Rui Liang; Fu Li Liu; Xiu Tao Sun; Fei Jiu Wang (Journal of Applied Phycology, 2019)

Pine needles as biomonitors of polybrominated diphenyl ethers and emerging flame retardants in the atmosphere of Shanghai, China: occurrence, spatial distributions, and possible sources - Hao-Hao Jia; Xue-Tong Wang; Hang-Xin Cheng; Ying Zhou; Rui Fu (Environmental Science and Pollution Research, 2019)

Genetic diversity and population structure of two endemic Cupressus (Cupressaceae) species on the Qinghai-Tibetan plateau - Yaru Fu; Shaoke Li; Qiqiang Guo; Weilie Zheng; Rui Yang; Huie Li (Journal of Genetics, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

The IMPDH inhibitors, ribavirin and mycophenolic acid, inhibit peste des petits ruminants virus infection - Qiu-yan Chang; Fu-cheng Guo; Xue-rui Li; Jian-hua Zhou; Xuepeng Cai; Qiuwei Pan; Xiao-xia Ma (Veterinary Research Communications, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

Mutation of I176R in the E coding region weakens Japanese encephalitis virus neurovirulence, but not its growth rate in BHK-21 cells - Yuyong Zhou; Rui Wu; Qin Zhao; Yung-Fu Chang; Xintian Wen; Yao Feng; Xiaobo Huang; Yiping Wen; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Archives of Virology, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Periodical drying or no drying during aquaculture affects the desiccation tolerance of a sublittoral Pyropia yezoensis strain - Xiao-lei Li; Wen-jun Wang; Fu-li Liu; Zhou-rui Liang; Xiu-tao Sun; Hai-qing Yao; Fei-jiu Wang (Journal of Applied Phycology, 2018)

Plasma circular RNA profiling of patients with gastric cancer and their droplet digital RT-PCR detection - Tianwen Li; Yongfu Shao; Liyun Fu; Yi Xie; Linwen Zhu; Weiliang Sun; Rui Yu; Bingxiu Xiao; Junming Guo (Journal of Molecular Medicine, 2018)

Flocculation of coal washing wastewater using polysaccharide produced by Paenibacillus mucilaginosus WL412 - Haiyang Xu; Jing Li; Renjie Fu; Rui Cheng; Shiming Wang; Jianfa Zhang (Environmental Science and Pollution Research, 2017)

Structural characteristics of atmospheric temperature and humidity inside clouds of convective and stratiform precipitation in the rainy season over East Asia - Rui Wang; Yunfei Fu (Journal of Meteorological Research, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Developmental and physiological properties of Pyropia dentata (Bangiales, Rhodophyta) conchocelis in culture - Zhi-hai Zhong; Wen-jun Wang; Xiu-tao Sun; Fu-li Liu; Zhou-rui Liang; Fei-jiu Wang; Wei-zhou Chen (Journal of Applied Phycology, 2016)

Suppressing Receptor-Interacting Protein 140: a New Sight for Salidroside to Treat Cerebral Ischemia - Tong Chen; Zhanqiang Ma; Lingpeng Zhu; Wenjiao Jiang; Tingting Wei; Rui Zhou; Fen Luo; Kai Zhang; Qiang Fu; Chunhua Ma; Tianhua Yan (Molecular Neurobiology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Bovine lactotroph cultures for the study of prolactin synthesis functions - Jianfa Wang; Zhanqing Yang; Shoupeng Fu; Bingrun Liu; Dianjun Wu; Wei Wang; Dongbo Sun; Rui Wu; Juxiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Combination of retinoic acid, dimethyl sulfoxide and 5-azacytidine promotes cardiac differentiation of human fetal liver-derived mesenchymal stem cells - Fuxue Deng; Han Lei; Yunfeng Hu; Linjing He; Hang Fu; Rui Feng; Panpan Feng; Wei Huang; Xi Wang; Jing Chang (Cell and Tissue Banking, 2016)

A climatological comparison of column-integrated water vapor for the third-generation reanalysis datasets - Yu Wang; Ying Zhang; YunFei Fu; Rui Li; YuanJian Yang (Science China Earth Sciences, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

Effect of abiotic stress on the gameophyte of Pyropia katadae var. hemiphylla (Bangiales, Rhodophyta) - Wen-Jun Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang; Ji-Hong Zhang; Fei-Jiu Wang (Journal of Applied Phycology, 2016)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Comparative genomic approach reveals novel conserved microRNAs in Inner Mongolia cashmere goat skin and longissimus dorsi - Rui Su; Shaoyin Fu; Yanjun Zhang; Ruijun Wang; Yanhong Zhou; Jinquan Li; Wenguang Zhang (Molecular Biology Reports, 2015)

Capecitabine plus oxaliplatin (XELOX) compared with 5-fluorouracil/leucovorin plus oxaliplatin (FOLFOXs) in advanced gastric cancer: meta-analysis of randomized controlled trials - Hong-Bin Xu; Fang Huang; Rui Su; Fu-Ming Shen; Qian-Zhou Lv (European Journal of Clinical Pharmacology, 2015)

Matching methods of classic hail echo cores of weather radar - Xue-tao Yu; Xiao-ping Rui; Shuang-xi Fu; Wei Liu (Natural Hazards, 2015)

Statures in Han populations of China - LianBin Zheng; YongLan Li; HuanJiu Xi; KeLi Yu; ShunHua Lu; Rui Shi; YouFeng Wen; JingPing Bao; XingHua Zhang; YuLing Li; Fu Ren; GuoChang Xu (Science China Life Sciences, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Detection and Analysis of 12 Heavy Metals in Blood and Hair Sample from a General Population of Pearl River Delta Area - Jiqiang Li; Dongzhi Cen; Donglan Huang; Xufeng Li; Jiajun Xu; Shilin Fu; Rui Cai; Xiaocong Wu; Ming Tang; Yao Sun; Jiren Zhang; Jingfen Zheng (Cell Biochemistry and Biophysics, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Daytime precipitation identification scheme based on multiple cloud parameters retrieved from visible and infrared measurements - XianTong Liu; Qi Liu; YunFei Fu; Rui Li (Science China Earth Sciences, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Erratum to: Coralslurrinella hongkonensis gen. nov., sp. nov., a novel bacterium in the family Psychromonadaceae, isolated from the coral Platygyra carnosus - Yanxia Li; Yuki Chan; Yingnan Fu; Rui Zhang; Jill M. Y. Chiu (Antonie van Leeuwenhoek, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

High-performance liquid chromatography with fluorescence detection for the determination of nitrofuran metabolites in pork muscle - Liang-Quan Sheng; Ming-Ming Chen; Shui-Sheng Chen; Na-Na Du; Zhao-Di Liu; Chong-Fu Song; Rui Qiao (Food Additives & Contaminants: Part A, 2013)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Coralslurrinella hongkonensis gen. nov., sp. nov., a novel bacterium in the family Psychromonadaceae, isolated from the coral Platygyra carnosus - Yanxia Li; Yuki Chan; Yingnan Fu; Rui Zhang; Jill M. Y. Chiu (Antonie van Leeuwenhoek, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Over-expression of l-galactono-γ-lactone dehydrogenase increases vitamin C, total phenolics and antioxidant activity in lettuce through bio-fortification - Xinbo Guo; Rui Hai Liu; Xueqing Fu; Xiaofen Sun; Kexuan Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Photodegradation of Tri (2-chloroethyl) Phosphate in Aqueous Solution by UV/H2O2 - Xin-Chao Ruan; Rui Ai; Xiao Jin; Qing-Fu Zeng; Ze-Yu Yang (Water, Air, & Soil Pollution, 2013)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Multiple Mesozoic mineralization events in South China—an introduction to the thematic issue - Rui-Zhong Hu; Mei-Fu Zhou (Mineralium Deposita, 2012)

Trichoderma biodiversity in China - Rui-yan Sun; Zhi-cheng Liu; Kehe Fu; Lili Fan; Jie Chen (Journal of Applied Genetics, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Mutations in isocitrate dehydrogenase 2 accelerate glioma cell migration via matrix metalloproteinase-2 and 9 - Yuejun Fu; Yali Zheng; Ke Li; Rui Huang; Shuhua Zheng; Na An; Aihua Liang (Biotechnology Letters, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Induced pluripotent stem cell-related genes influence biological behavior and 5-fluorouracil sensitivity of colorectal cancer cells - Zhong Shi; Rui Bai; Zhi-xuan Fu; Yong-liang Zhu; Rong-fu Wang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

A potential strategy for high-grade gliomas: combination treatment with lithium chloride and BmK CT - Yuejun Fu; Shuhua Zheng; Rui Huang; Na An; Yali Zheng; Zhiyun Zhang; Aihua Liang (Biotechnology Letters, 2012)

Identification of a Novel Bacterial K+ Channel - Guanghua Tang; Bo Jiang; Yuan Huang; Ming Fu; Lingyun Wu; Rui Wang (The Journal of Membrane Biology, 2011)

Azoospermia related to a unique karyotype: 45,XY,−13,−19,+der(19)t(13;19)(q12;p13) - Chao Fu; Xin Yun; Yuan Dong; Bai-Yan Wu; Rong-Rong Han; Rui-Zhi Liu (Journal of Applied Genetics, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Paracoccus beibuensis sp. nov., Isolated from the South China Sea - Qiang Zheng; Yanan Wang; Chuang Chen; Yu Wang; Xiaomin Xia; Yingnan Fu; Rui Zhang; Nianzhi Jiao (Current Microbiology, 2011)

Diversity, abundance and characterization of ruminal cysteine phytases suggest their important role in phytate degradation - Huoqing Huang; Rui Zhang; Dawei Fu; Jianjie Luo; Zhongyuan Li; Huiying Luo; Pengjun Shi; Peilong Yang; Qiyu Diao; Bin Yao (Environmental Microbiology, 2011)
Summary A novel class of cysteine phytase showing ability to degrade phytate has recently been isolated from rumen bacteria. To expand our knowledge of this enzyme class, a total of 101 distinct cysteine phytase gene fragments were identified from the ruminal genomic DNA of Bore goats and Holstein cows, and most of them shared low identities (

Nash model parameter uncertainty analysis by AM-MCMC based on BFS and probabilistic flood forecasting - Zhenxiang Xing; Xiaofang Rui; Qiang Fu; Yi Ji; Shijiang Zhu (Chinese Geographical Science, 2011)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Isopentenyl transferase gene (ipt) downstream transcriptionally fused with gene expression improves the growth of transgenic plants - Jian-Chun Guo; Rui-Jun Duan; Xin-Wen Hu; Kai-Mian Li; Shao-Ping Fu (Transgenic Research, 2010)

Evolution of viviparity in cold-climate lizards: testing the maternal manipulation hypothesis - Hong Li; Yan-Fu Qu; Rui-Bin Hu; Xiang Ji (Evolutionary Ecology, 2009)

Embryo and anther regulation of the mabinlin II sweet protein gene in Capparis masaikai Lévl - Xin-Wen Hu; Si-Xin Liu; Jian-Chun Guo; Ji-Tao Li; Rui-Jun Duan; Shao-Ping Fu (Functional & Integrative Genomics, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

A value chain approach to crisis response system: the case of Qingdao - Jian Hua Li; Zheng Ping Zhang; Rui Huan Jing; Chong Fu Huang (Stochastic Environmental Research and Risk Assessment, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Group Time Delay in the Reflection of P-Polarized Electromagnetic Plane Waves at a Stratigraphic Interface - Fu-Ping Liu; Rui-Zhong Li; Jin-yao Li; Hui-Guo Chen; Chang-Chun Yang (Mathematical Geosciences, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)

Tropical precipitation estimated by GPCP and TRMM PR observations - Li Rui; Fu Yunfei (Advances in Atmospheric Sciences, 2005)

Induced Activity of Superoxide Dismutase and Peroxidase of in vitro Plants by Low Concentrations of Ethanol - Xiu-Qing Li; Shi-Hua Li; De-Fu Chen; Fan-Rui Meng (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Evolution of urban system in new economic circumstances and planning countermeasures - Jing-xiang Zhang; Qi-yan Wu; Fu-hong Rui (Chinese Geographical Science, 2001)